Composition for waterproof film

By using a composition of powdered pozzolan material, Bortland cement clinker and a water-based polymer with low glass transition temperature, the problems of cement-based waterproof films in terms of flexibility and corrosion resistance are solved, and high bond strength is achieved and waterproof membrane with low carbon footprint.

CN119301087APending Publication Date: 2025-01-10BASF SE
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202380043975.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing cement-based waterproof membrane is not satisfied with its flexibility and crack bridging ability, especially under low temperature conditions, and its production process has a large carbon footprint and energy consumption to the environment, and is insufficient to withstand acidic and corrosive substances. .

Method used

Using a composition containing powdered pozzolan material, Bortland cement clinker and an aqueous polymer with low glass transition temperature, the high bond strength and corrosion resistance are formed by adjusting the component ratio and adding appropriate fillers and unslaked lime. waterproof membrane.

Benefits of technology

A waterproof film with high flexibility and good crack bridging ability under low temperature conditions is realized, while reducing production energy consumption and carbon emissions, and improving tolerance to acidic and alkaline substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161182450000301
    Figure BDA0005161182450000301
  • Figure BDA0005161182450000341
    Figure BDA0005161182450000341
  • Figure BDA0005161182450000351
    Figure BDA0005161182450000351
Patent Text Reader

Abstract

The invention relates to a composition for producing a waterproof film, comprising: a) as component A a powdered pozzolanic material comprising at least 15% by weight, in particular at least 20% by weight, in particular at least 25% by weight or at least 30% by weight, based on the total amount of component A of the powdered pozzolanic material; b) as component B a pulverulent cement comprising a Portland cement clinker in an amount of at least 15% by weight, in particular at least 25% by weight, in particular at least 35% by weight or at least 45% by weight, relative to the total amount of component B; c) at least one powdered filler as component C; d) an organic polymer P in the form of an aqueous polymer dispersion or in the form of a polymer powder as component D, the polymer P having a glass transition temperature Tg in the range of at most + 10 DEG C, in particular at most + 5 DEG C, preferably in the range of-30 DEG C to + 10 DEG C, in particular in the range of-20 DEG C to + 5 DEG C, as determined by the differential scanning calorimetry (DSC) method according to ISO 11357-2: 2013; wherein the weight ratio of the tuff to the Portland cement clinker is in the range of from 5: 95 to 95: 5, in particular in the range of from 10: 90 to 90: 10, in particular in the range of from 20: 80 to 80: 20. The invention also relates to the use of said composition for providing a waterproof film. Furthermore, the present invention relates to a method for providing a waterproof film comprising providing a composition as described herein in the form of an aqueous slurry of the components of the composition, the present invention relates to an aqueous slurry comprising a polymer P, for example by mixing the components of the composition with water or by mixing a powdered composition comprising component A, component B and component C and optionally other powdered components with an aqueous dispersion of the polymer P, and applying the aqueous slurry to a surface in need of a water-repellent covering, for example by mixing the components of the composition with water or by mixing a powdered composition comprising component A, component B and component C and optionally other powdered components with an aqueous dispersion of the polymer P. The waterproof film is obtained when the coating thus obtained hardens.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a composition for producing waterproof membranes, comprising a pozzolanic material, at least one pulverulent filler and an organic polymer P in the form of an aqueous polymer dispersion or a polymer powder obtained therefrom having a glass transition temperature of at most +15°C. Background Art

[0002] In construction, waterproofing membranes used for example for drains (such as sewage or rainwater drains and pipelines), for waterproofing of buildings and building parts, for example for waterproofing of basements or as a waterproof layer under tiles in wet rooms (such as bathrooms), swimming pools or water tanks are usually based on cement-organic polymer systems. Due to the presence of cement binders and optional mineral fillers, they are also called mineral coverings. Typically, the composition for waterproofing membranes contains a cement binder of cement group CEM I (ordinary Portland cement, also referred to as OPC) according to EN 197-1:2011, in particular a fast-setting type or a mixture thereof, as the main component of the mineral binder. Alternatively, calcium aluminate cements, in particular high alumina cement (HAC), calcium sulfoaluminate cement (CSA) and combinations thereof with OPC have been suggested as mineral binders. Combinations of OPC, HAC and gypsum have also been described for fast-setting compositions. However, these systems usually require lithium-based accelerators, such as lithium carbonate, which are expensive and have limited availability due to the high demand for electrical mobility.

[0003] Compositions for waterproofing membranes containing OPC as mineral binder have been frequently described, for example in US 2018 / 0179108.

[0004] WO 2016 / 142339 describes a composition for sealing slurry, comprising a hydraulic binder, silica sand, limestone powder and a polymer, wherein the hydraulic binder comprises calcium aluminate cement, in particular high alumina cement (HAC), calcium sulfoaluminate cement (CSA) or a mixture thereof.

[0005] US2018 / 0327310 describes a two-component composition for preparing a waterproof membrane, comprising an emulsion polymer as one component and a fast-curing dry-mixed powder composition of conventional OPC and high-alumina cement as separate components.

[0006] However, mineral waterproofing membranes based on these cement-polymer systems are not satisfactory in terms of their flexibility or elasticity, which is reflected in unsatisfactory crack bridging capabilities, especially at low temperatures, which may be due to the rapid setting of typical cement-based bonding systems. Good crack bridging properties are important not only for the resistance of waterproofing membranes to mechanical or temperature stresses, but also for the suitability of such systems as repair materials, for example, for water-containing structures, such as rainwater drains or sewage pipes. In addition, these cement-based systems become brittle over time, because the cement contained therein is only partially converted and thus undergoes post-reactions. Furthermore, mineral waterproofing membranes based on cement-polymer systems are not completely satisfactory in terms of their resistance to acidic and corrosive substances.

[0007] In addition, there is an urgent need to reduce the production and consumption of cement. The currently popular type of cement, hydraulic cement, is obtained by sintering limestone and aluminosilicate materials (such as clay) at about 1450°C. During sintering, the limestone (CaCO3) is calcined into lime (CaO), releasing CO2. Considering the high energy consumption for providing the required temperatures (usually by burning fossil fuels), the CO2 formation inherently from the calcination process and from energy production, and of course the sheer amount used worldwide in construction, cement production has become a huge source of world CO2 emissions. It is therefore desirable to replace cement at least partially with materials that have a smaller carbon footprint.

[0008] Earlier patent application PCT / EP2021 / 083482 describes a 2K composition for providing a waterproof membrane, the composition comprising a pozzolanic material (such as volcanic tuff), non-hydrated lime and a film-forming polymer having a glass transition temperature of at most +15°C. Summary of the invention

[0009] The object of the present invention is to provide a composition for waterproofing applications, in particular for waterproofing membranes, which composition is waterproof after setting, is resistant to acidic and alkaline substances and to other corrosive substances (in particular chlorine-containing substances), has high elasticity or flexibility, manifested in, for example, good crack bridging ability, especially at low temperatures, and has high bond strength. The setting time should also be satisfactory, and the composition should not tend to become brittle over time. In addition, its production will be less energy intensive and should reduce CO2 release compared to cement binder systems. In addition, it should be possible to combine with recycled materials (for example brick dust or powdered rubber), thereby reducing the amount of mineral fillers (such as sand), the natural reserves of which have been lost recently.

[0010] This object is achieved by a composition comprising: a powdered pozzolanic material comprising powdered rough tuff as component A; a powdered cement comprising portland cement clinker as component B, wherein the weight ratio of rough tuff to portland cement clinker of component B is in the range of 5:95 to 95:5; one or more powdered fillers; and a polymer based on ethylenically unsaturated monomers having a glass transition temperature Tg of at most +10°C.

[0011] Therefore, the present invention relates to a composition for producing a waterproof membrane, the composition comprising

[0012] a) a pulverulent pozzolanic material as component A, which comprises at least 15% by weight, in particular at least 20% by weight, in particular at least 25% by weight or at least 30% by weight of pulverulent trachyte, based on the total amount of component A of the pulverulent pozzolanic material;

[0013] b) powdered cement as component B, which comprises portland cement clinker in an amount of at least 15% by weight, in particular at least 25% by weight, especially at least 35% by weight or at least 45% by weight, based on the total amount of component B;

[0014] c) at least one pulverulent filler as component C;

[0015] d) an organic polymer P as component D in the form of an aqueous polymer dispersion or in the form of a polymer powder, wherein the polymer P has a glass transition temperature Tg of at most +10°C, in particular at most +5°C, preferably in the range from -30°C to +10°C, especially in the range from -20°C to +5°C, as determined by the differential scanning calorimetry (DSC) method in accordance with ISO 11357-2:2013;

[0016] The weight ratio of the trachyte to the portland cement clinker is in the range of 5:95 to 95:5, in particular in the range of 10:90 to 90:10, and in particular in the range of 20:80 to 80:20.

[0017] The invention also relates to the use of said composition for providing a waterproof membrane.

[0018] Furthermore, the present invention relates to a method for providing a waterproof membrane, which method comprises providing a composition as described herein in the form of an aqueous slurry of the components of the composition, for example by mixing the components of the composition with water or by mixing a pulverulent composition comprising the components A, B and C and optionally other pulverulent components with an aqueous dispersion of the polymer P, and applying the aqueous slurry to a surface requiring a waterproof covering. When the coating thus obtained hardens, the waterproof membrane is obtained. DETAILED DESCRIPTION

[0019] The composition of the present invention is not necessarily a physical mixture of component A, component B, component C and component D and optional other components disclosed herein, but can constitute any desired combination of sub-compositions or their components, wherein they are not necessarily formulated together. An example of a composition is a two-component kit, which comprises a first composition (I) containing component A, component B and component C and a second composition (II) containing component D. For example, when the components of one of the compositions interfere with one or more components of another composition, this composition form is advantageous. For example, if composition (II) is aqueous, the water contained therein can start the reaction of component A and component B, and of course, this reaction is prevented until the composition is put into use at a desired time point. The first composition can also be mainly formulated as a kit, but is preferably formulated as a physical mixture. The composition of the present invention can also be formulated as a 1K formulation of a polymer P in the form of a polymer powder. In addition, component A and component B can be formulated as a first powdery composition, and component C and component D and optional water are added immediately before the composition is used to provide an aqueous slurry for forming a waterproof film.

[0020] The term "pozzolanic material" refers to natural and artificial volcanic ashes. Pozzolanic ashes are natural or artificial siliceous or siliceous and aluminous rock materials and have been used as building materials since ancient times, for example in ancient Rome as natural concrete (opus caementitium). They are generally formed from silicon dioxide, clay, limestone, iron oxide and alkaline materials under heating. They themselves have little or no value as a binder, but in finely divided form and in the presence of water, react chemically with calcium hydroxide at normal temperatures to form a material having cementitious properties.

[0021] Natural volcanic ashes are igneous rocks, such as volcanic tuff or volcanic trachytuff, or sedimentary rocks containing large amounts of soluble silicic acid and partly alumina (clay). Other sources of volcanic ashes are derived from rock deformations caused by meteorite impacts, such as the Bavarian trachytuff, the Rees trachytuff or the Suevit. Trachytuffs can therefore be volcanogenic or derived from meteorite impacts. Strictly speaking, volcanic trachytuff is a volcanic tuff of volcanic ashes, which originates from the volcanic eruption of the Laacher See volcano in the Eifel, Germany and occurs in the Broll and Nette valleys. However, in the present invention, "volcanic trachytuff" relates to any volcanic tuff of volcanic ashes, regardless of its origin.

[0022] Artificial pozzolans are, for example, brick dust; or fly ash, such as is obtained from power stations burning lignite or hard coal; waste slags, such as blast furnace slag and steelmaking slag, which are obtained from the manufacture of steel.

[0023] The term "unslaked lime" refers to calcium oxide (CaO) and may also be referred to as burnt lime or quicklime.

[0024] Generally, the term "powdery" with respect to a pulverulent material means that the material has a particle size of at most 1000 μm, in particular at most 750 μm.

[0025] For example, "powdery" pozzolanic material means that the pozzolanic material has a particle size of at most 500 μm, in particular at most 300 μm, preferably at most 250 μm or at most 200 μm, in particular at most 100 μm.

[0026] "Powdered" cement means cement having a particle size of at most 500 μm, in particular at most 400 μm, preferably at most 300 μm or at most 250 μm, in particular at most 200 μm.

[0027] "Powdery" non-slaked lime means that the non-slaked lime has a particle size of at most 500 μm, in particular at most 300 μm, preferably at most 250 μm or at most 200 μm, in particular at most 100 μm.

[0028] The particle size in the filler is not very critical and can be somewhat larger than the particles of the pulverulent components A and B. It is generally at most 1000 μm, in particular at most 700 μm.

[0029] The polymer P of component D can be used in the composition as a polymer powder or as an aqueous polymer dispersion. If the polymer P of component D is present in the form of a polymer powder, the particle size of the polymer powder is not very critical, but is such that the polymer powder can be easily dispersed in water. It is generally within the ranges given above for the pozzolanic material and generally has a particle size of at most 300 μm or at most 250 μm or at most 200 μm.

[0030] The particle size and particle size distribution can be determined using a variety of measurement methods known per se to the person skilled in the art, for example via sieve analysis according to DIN 66165-2:2016-08, sedimentation or light scattering, for example laser diffraction according to DIN ISO 13321:2004-10. In the present case, the given particle size of the components of the pulverulent composition A is the particle size indicated by the commercial manufacturer or determined using sieve analysis according to DIN 66165-2:2016-08.

[0031] The following description of suitable and preferred embodiments of the present invention, in particular of suitable and preferred features of the components of the compositions of the present invention and their use, applies both on its own and in any combination with each other.

[0032] According to the invention, the pozzolanic material comprises trachyte (of course in powder form). Among the trachyte tuffs, volcanic trachyte tuffs are preferred. More preferred is volcanic trachyte tuffs. Trachyte tuffs, in particular volcanic trachyte tuffs, account for at least 15% by weight, in particular at least 20% by weight, preferably at least 25% by weight, especially at least 30% by weight of the total amount of pozzolanic material of component A, and may account for up to 100% by weight of component A. Component A is substantially free of non-pozzolanic cement, i.e. the amount of non-pozzolanic cement in component A is at most 10% by weight, in particular at most 5% by weight, based on the total weight of component A.

[0033] In a particular embodiment, the pozzolanic material also comprises an artificial pozzolanic material, such as brick dust or fly ash obtained, for example, from a power station burning lignite or hard coal. The artificial pozzolanic material is preferably brick dust or powdered slag. Brick dust (also called brick dust or clay powder) is preferably a recycled material, which is obtained, for example, by crushing brick waste (for example discarded building bricks and roof tiles). Powdered slag is ground slag, for example ground slag, such as ground blast furnace slag and ground steelmaking slag obtained from the manufacture of steel. The artificial pozzolanic material not only reduces the amount of natural pozzolanic ash, thereby allowing the conservation of the original natural resource, but also contributes to the flexibility and elasticity of the solidification system and therefore to the crack resistance.

[0034] In a preferred embodiment, the pozzolanic material comprises or consists of:

[0035] i. 15% to 90% by weight, based on the total amount of pozzolanic material, of powdered trachyte, in particular powdered volcanic trachyte; and

[0036] ii. 10 to 85% by weight, based on the total amount of pozzolanic material, of pulverulent artificial pozzolanic material, in particular brick dust,

[0037] The total amount of powdered trachyte and brick dust, based on the total amount of component A, is preferably at least 90% by weight, in particular at least 95% by weight.

[0038] More preferably, the pozzolanic material comprises or consists of:

[0039] i. 20% to 85% by weight, based on the total amount of pozzolanic material, of powdered trachyte, in particular powdered volcanic trachyte; and

[0040] ii. 15 to 80% by weight, based on the total amount of pozzolanic material, of pulverulent artificial pozzolanic material, in particular brick dust,

[0041] The total amount of powdered trachyte and brick dust, based on the total amount of component A, is preferably at least 90% by weight, in particular at least 95% by weight.

[0042] More preferably, the pozzolanic material comprises or consists of:

[0043] i. 25 to 80% by weight, based on the total amount of pozzolanic material, of powdered trachyte, in particular powdered volcanic trachyte; and

[0044] ii. 20% to 75% by weight, based on the total amount of pozzolanic material, of pulverulent artificial pozzolanic material, in particular brick dust,

[0045] The total amount of powdered trachyte and brick dust, based on the total amount of component A, is preferably at least 90% by weight, in particular at least 95% by weight.

[0046] More preferably, the pozzolanic material comprises or consists of:

[0047] i. 30% to 75% by weight, based on the total amount of pozzolanic material, of powdered trachyte, in particular powdered volcanic trachyte; and

[0048] ii. 25 to 70% by weight, based on the total amount of pozzolanic material, of pulverulent artificial pozzolanic material, in particular brick dust,

[0049] The total amount of powdered trachyte and brick dust, based on the total amount of component A, is preferably at least 90% by weight, in particular at least 95% by weight.

[0050] As already explained above, the pozzolanic material has a particle size of at most 500 μm, in particular at most 300 μm, preferably at most 250 μm or at most 200 μm. In the case of volcanic trachyte or tuff, the material has in particular a particle size of at most 250 μm, more in particular at most 200 μm, in particular at most 100 μm.

[0051] Preferably, the trachyte has a thickness of at least 5000 cm 2 / g, more preferably 5500cm 2 / g to 8500cm 2 / g, especially 6500cm 2 / g to 7500cm 2 / g of Blaine specific surface area.

[0052] According to the invention, the composition contains as component B at least one powdered cement, which contains portland cement clinker in an amount of at least 15% by weight, based on the total weight of component B. According to EN 197-1:2011, these cements are also named ordinary cements. Preference is given to ordinary cements containing at least 25% by weight, in particular at least 35% by weight, especially at least 45% by weight of portland cement clinker, based on the total weight of component B. Component B particularly includes cements selected from the group consisting of ordinary cements classified as CEM I, CEM II, CEM IV and CEM V and mixtures thereof. The terms CEM I, CEM II, CEM IV and CEM V refer to the cement classifications according to EN 197-1:2011.

[0053] As observed by the present inventors, the presence of sufficient amounts of Portland cement clinker in the composition of the present invention instead of slaked lime commonly used in pozzolanic systems results in significantly faster setting.

[0054] In a particularly preferred set of embodiments, the cement component B is a cement classified as CEM I. According to cement classification EN 197-1:2011, CEM I type cement contains at least 95% of portland cement clinker. Such cements are generally referred to as ordinary portland cement (OPC). CEM I type cement may be any type of OPC, including portland cement classified as CEM I 52.5N, CEM I 42.5N, CEM I 32.5N, CEM I 52.5R, CEM I 42.5R or CEM I 32.5R.

[0055] Component B may also be a cement comprising 65 wt % to <95 wt % of portland cement clinker and >5 wt % to 35 wt % of cementitious substances other than portland cement clinker, such as slag, granulated blast furnace slag, fly ash, natural or naturally calcined pozzolanic materials, silica powder, metakaolin, limestone and calcined oil shale. These cements are usually classified as cement CEMII according to cement classification EN 197-1:2011, and include portland slag cement, portland silica fume cement, portland pozzolanic cement, portland fly ash cement, portland burned shale cement, portland limestone cement and portland composite cement.

[0056] In another specific set of embodiments, component B is a CEM IV type cement, i.e. a pozzolanic cement. In this case, the rough tuff of component A may be present as a mixture with the portland cement clinker in the weight ratios given above. In this case, a portion or all of the rough tuff of component A may be included in the cement of component B, thus being a mixture containing both portland cement clinker and rough tuff. In other words, the rough tuff of component A and the portland cement clinker of component B may be premixed to form a CEM IV group cement.

[0057] In any case, the weight ratios of trachyte tuff and portland cement clinker in the composition of the present invention are within the ranges given herein.

[0058] Part of component B can be replaced by another hydraulic binder (hereinafter referred to as component B'), such as gypsum, calcium sulfoaluminate cement (CSA) and / or calcium aluminate cement (HAC), provided that the amount of portland cement clinker and its ratio to rough tuff are as given above. Preferably, the relative amount of component B will be at least 60% by weight, in particular at least 75% by weight, and can be up to 100% by weight, based on the total weight of component B and component B' in the composition of the invention. In particular, component B' is absent or in an amount of less than 5% by weight, based on the total weight of component B and component B' in the composition of the invention.

[0059] In the composition of the present invention, the weight ratio of trachyte to portland cement clinker is in the range of 5:95 to 95:5, in particular in the range of 10:90 to 90:10, preferably in the range of 20:80 to 80:20, in particular in the range of 30:70 to 70:30.

[0060] In the composition of the invention, especially if component A and component B are provided separately, the weight ratio of component A to component B is preferably in the range of 25:75 to 95:5, in particular in the range of 30:70 to 85:15, especially in the range of 40:60 to 80:20.

[0061] The total amount of component A is preferably in the range of 25% to 50% by weight, in particular in the range of 30% to 45% by weight, based on the total weight of component A, component B, optionally B' and C. In a specific embodiment, the composition comprises 10% to 40% by weight, in particular 15% to 30% by weight, based on the total weight of component A, component B and component C and optionally B', of trachyte and 10% to 40% by weight, in particular 15% to 30% by weight, based on the total weight of component A, component B and component C and optionally B', of brick dust.

[0062] The total amount of component A and component B and optionally B′ is preferably in the range from 35 to 65% by weight, in particular in the range from 40 to 60% by weight, based on the total weight of component A, component B and component C and optionally B′.

[0063] Component C (hereinafter also referred to as filler) generally comprises granular mineral material, in particular granular stone which is generally used as reinforcing material to increase the strength of the entire composite material. The filler used in the composition of the present invention can be any common building filler, including mineral fillers, such as rock powder and sand; and recycled fillers produced by recycling of concrete, which itself is mainly made of mineral fillers. Mineral fillers such as powdered dolomite, granite, gravel, sandstone, limestone, basalt, etc. can also be used as fillers. The powdered filler of the present invention can also be an organic concrete "filler", such as rubber or asphalt. The powdered filler of the present invention generally also includes a mixture of two or more of the fillers listed above.

[0064] The total amount of pulverulent fillers is preferably in the range from 35 to 65% by weight, in particular in the range from 40 to 60% by weight, based on the total weight of components A, B and C and optionally B′.

[0065] Preferably, the pulverulent filler comprises sand. Preferably, the pulverulent filler comprises, based on the total weight of component C, preferably at least 50% by weight, more preferably at least 60% by weight and at most 100% by weight of sand.

[0066] Preferably, the sand is a combination of medium sand and fine sand. For the purposes of the present invention, fine sand is defined in accordance with DIN 4022:1987 and is sand with an equivalent diameter of 0.063 mm to 0.2 mm. For the purposes of the present invention, medium sand is defined in accordance with DIN 4022:1987 and is sand with an equivalent diameter of 0.2 mm to 0.63 mm. Medium sand and fine sand are preferably present in a weight ratio of 2:1 to 1:5, more preferably 1:1 to 1:3, in particular 1:1.5 to 1:3.

[0067] In a preferred embodiment, the filler comprises an organic powdered recycled material, such as powdered rubber. Powdered rubber is a recycled material obtained, for example, by pulverizing discarded tires or the like. Powdered rubber not only reduces the amount of natural mineral fillers (such as sand), thereby allowing the conservation of their original natural resources, but also contributes to the flexibility and elasticity of the coagulation system, and therefore to crack resistance. The organic powdered recycled material preferably has a particle size of at most 500 μm and usually at least 50 μm.

[0068] The organic powdery recycled material, if included in the composition, is preferably present in an amount of 5 to 50 wt. %, more preferably 10 to 40 wt. %, in particular 10 to 35 wt. %, based on the total weight of component C. If present, the amount of organic powdery recycled material is generally in the range of 2 to 25 wt. %, in particular 5 to 15 wt. %, based on the total weight of component A, component B and component C and optionally B'.

[0069] In addition to component A, component B, component C and component D (and optionally B'), the composition may also contain other ingredients. An example of an additional ingredient is kaolin, hereinafter referred to as component E. As observed, the presence of kaolin leads to a fibrous structure of the solidified system, which enhances its flexibility and crack stability. Therefore, in a preferred embodiment, the composition of the present invention also contains powdered kaolin. Kaolin (also known as clay) is a hydrated aluminum silicate that can be approximately described by a simple and idealized chemical formula Al2O3·2SiO2·2H2O. It is a natural, fine-grained and well-crystallized clay mineral with a layered structure. Kaolin (if included in the composition) is preferably present in an amount of 1% to 10% by weight, more preferably 1% to 5% by weight, and particularly 2% to 3% by weight, based on the total weight of component A, component B and component C and optional B'. Kaolin preferably has a particle size of at most 500 μm, more preferably at most 300 μm, and particularly at most 100 μm.

[0070] The composition of the invention may also contain non-slaked lime as component F. As observed by the inventors, the use of non-slaked lime in the composition of the invention leads to significantly faster setting. In addition, it allows the amount of calcium required for setting to be reduced. If present, the amount of non-slaked lime is preferably in the range of 5% to 20% by weight, in particular in the range of 8% to 15% by weight, based on the total weight of component A, component B and component C and optionally B'.

[0071] A particular set of embodiments of the present invention relates to compositions containing no non-hydrated lime or less than 5 wt. % non-hydrated lime, based on the total weight of component A, component B and component C and optionally B'.

[0072] In addition, the composition of the invention may contain other additives commonly used for such formulations, such as rheology modifiers (e.g. thickeners, plasticizers), accelerators or retarders (for the setting process) and wetting agents or dispersants, respectively. These additives are referred to below as component G. The total amount of these additives is generally at most 5% by weight, preferably at most 2% by weight, based on the total weight of component A, component B and component C and optionally B', and if present, for example in the range of 0.1% to 5% by weight or in the range of 0.2% to 2% by weight.

[0073] Here, the terms "wetting agent" and "dispersant" are used synonymously. They allow to reduce the amount of make-up water required for the production of the slurry. Suitable wetting agents or dispersants are, for example, sodium polyphosphate, potassium polyphosphate or ammonium polyphosphate, alkali metal salts and ammonium salts of acrylic acid or maleic anhydride polymers, polyphosphonates (such as sodium 1-hydroxyethane-1,1-diphosphonate) and salts of naphthalenesulfonic acid, more particularly their sodium salts. Among the above-mentioned dispersants, preferred are polymeric dispersants, such as alkali metal salts and ammonium salts of acrylic acid polymers or maleic anhydride polymers. In particular, metal salts of polyacrylic acid are used as dispersants or wetting agents, respectively.

[0074] Preferably, the composition of the invention contains a dispersant, in particular a polymeric dispersant, in an amount of 0.1% to 5% by weight, in particular 0.3% to 3% by weight, based on the total weight of component A and component B.

[0075] In one preferred set of embodiments, the composition is formulated as a 2K composition comprising a first powdery composition (I) containing powdery components A, B and C and optionally powdery components B', E, F and G; and a second composition (I) containing a polymer P, in particular in the form of an aqueous polymer dispersion.

[0076] Typically, the composition (I) comprises or consists of:

[0077] (a) 25 to 50 wt. % of component A, in particular a combination of volcanic trachyte and brick dust;

[0078] (b) 10 to 40 wt % of component B or a combination of component B and component B′;

[0079] (c) 35 to 65% by weight of filler (component C), in particular a combination of sand and organic powdery recycled material (in particular powdered rubber);

[0080] (e) 0 to 10% by weight, for example 1 to 10% by weight, in particular 1 to 5% by weight, of powdered kaolin;

[0081] (f) 0 to 20% by weight of powdered unslaked lime;

[0082] (g) 0 to 5% by weight of other additives; in particular rheology modifiers, especially thickeners;

[0083] wherein the above percentages add up to 100 weight %, wherein the total amount of component A and component B and optionally B' is preferably in the range of 35 weight % to 65 weight %, in particular in the range of 40 weight % to 60 weight %, and wherein the weight ratio of the rough tuff of component A to the cement clinker of component B is preferably in the range of 10:90 to 90:10, in particular in the range of 20:80 to 80:20, and especially in the range of 30:70 to 70:30.

[0084] Specifically, the composition (I) comprises or consists of the following:

[0085] (a) 30 to 45 wt % of component A, in particular a combination of volcanic trachyte and brick dust;

[0086] (b) 15 to 35 wt % of component B or a combination of component B and component B′;

[0087] (c) 40 to 55% by weight of filler (component C), in particular a combination of sand and organic powdery recycled material (in particular powdered rubber);

[0088] (e) 1 to 10% by weight, in particular 1 to 5% by weight, of powdered kaolin;

[0089] (f) 0% to 15% by weight of powdered unslaked lime;

[0090] (g) 0 to 2% by weight of other additives; in particular rheology modifiers, especially thickeners;

[0091] wherein the above percentages add up to 100 weight %, wherein the total amount of component A and component B and optionally B' is preferably in the range of 45 weight % to 59 weight %, and wherein the weight ratio of the rough tuff of component A to the cement clinker of component B is preferably in the range of 10:90 to 90:10, in particular in the range of 20:80 to 80:20, and especially in the range of 30:70 to 70:30.

[0092] In a particular embodiment, the composition comprises or consists of:

[0093] (a.1) 10% to 40% trachyte, especially volcanic trachyte;

[0094] (a.2) 10 wt % to 40 wt % of brick powder;

[0095] wherein the total weight of trachyte tuff and brick dust is in the range of 25 wt % to 50 wt %;

[0096] (b) 10 to 40 wt % of component B or a combination of component B and component B′;

[0097] (c.1) 25 to 63 wt. % sand;

[0098] (c.2) 2 to 25 wt. % of powdered rubber; and

[0099] (e) 0 to 10% by weight, for example 1 to 10% by weight, in particular 1 to 5% by weight, of kaolin;

[0100] (f) 0 to 20% by weight of unslaked lime

[0101] (g) 0 to 5% by weight of other additives; in particular rheology modifiers, especially thickeners;

[0102] wherein the above percentages add up to 100 weight %, wherein the total amount of component A and component B is preferably in the range of 35 weight % to 65 weight %, in particular in the range of 40 weight % to 60 weight %, and wherein the weight ratio of the trachyte of component A to component B is preferably in the range of 10:90 to 90:10, in particular in the range of 20:80 to 80:20, and especially in the range of 30:70 to 70:30.

[0103] In a very specific embodiment, the composition comprises or consists of:

[0104] (a.1) 15% to 30% trachyte, especially volcanic trachyte;

[0105] (a.2) 14 wt % to 30 wt % of brick dust;

[0106] wherein the total weight of trachyte and brick dust is in the range of 30 wt % to 45 wt %,

[0107] (b) 15 to 35 wt % of component B or a combination of component B and component B′;

[0108] (c.1) 30 to 50 wt. % sand;

[0109] (c.2) 5 to 15% by weight of powdered rubber; and

[0110] (e) 1 to 10% by weight, in particular 1 to 5% by weight, of kaolin;

[0111] (f) 0 to 15% by weight of unslaked lime

[0112] (g) 0 to 2% by weight of other additives; in particular rheology modifiers, especially

[0113] Thickener;

[0114] wherein the aforementioned percentages add up to 100 weight %, wherein the total amount of component A and component B and optionally B' is preferably in the range of 44 weight % to 60 weight %, and wherein the weight ratio of trachyte of component A to component B is preferably in the range of 10:90 to 90:10, in particular in the range of 20:80 to 80:20, and in particular in the range of 30:70 to 70:30.

[0115] The composition of the invention further comprises a polymer P. The polymer P of component B can be present as an aqueous polymer dispersion or as a polymer powder, in particular a polymer powder obtained by spray drying of an aqueous polymer dispersion of polymer P.

[0116] The polymer P is made from polymerized ethylenically unsaturated monomers M, wherein the polymer has a glass transition temperature Tg of at most +15°C, in particular at most +10°C, more in particular at most +5°C, and especially at most 0°C. Here and in this specification, the values ​​given for the glass transition temperature Tg refer to the values ​​determined by the differential scanning calorimetry (DSC) method according to ISO 11357-2:2013, preferably using a sample preparation according to ISO 16805:2003. In the case where the polymer P is pulverulent, it comprises a polymer powder obtained from the above-mentioned aqueous polymer dispersion, wherein the polymer of the aqueous polymer dispersion has a glass transition temperature Tg of at most +15°C, in particular at most +10°C, more in particular at most +5°C, and especially at most 0°C. Typically, the glass transition temperature Tg is at least -60°C, typically at least -50°C, in particular at least -40°C, more in particular at least -30°C, and especially at least -25°C. Typically, the polymer has a Tg in the range of -60°C to +15°C. Preferably, the polymer has a Tg in the range of -50°C to +10°C, in particular in the range of -40°C to +5°C or -30°C to +5°C, in particular in the range of -30°C to 0°C or -25°C to 0°C.

[0117] The following remarks concerning polymers apply to both liquid and powder forms of polymer P.

[0118] The amount of polymer P of component D in the composition is generally such that the weight ratio of polymer P to the total weight of component A, component B, component C and, if present, optional component E and component F is in the range of 1:10 to 1:1, in particular in the range of 1:6 to 1:1.1. Preferably, the organic polymer P is present in the composition for producing waterproof membranes in an amount in the range of 10% to 50% by weight, in particular in the range of 15% to 45% by weight, based on the total weight of the dry matter of the composition for producing waterproof membranes and calculated as polymer P.

[0119] The polymer P is insoluble in water and is present in the form of discrete polymer particles.

[0120] If the polymer P is present in the form of an aqueous polymer dispersion of polymer particles of the polymer P, the average diameter of the polymer particles present in the aqueous dispersion is generally in the range of 10 nm to 1000 nm, generally in the range of 20 nm to 850 nm, for example in the range of 100 nm to 700 nm. The average particle size in this specification means the Z average particle size determined by dynamic light scattering (also known as quasi-elastic light scattering) of an aqueous polymer dispersion diluted to 0.001 wt % to 0.5 wt % with deionized water by means of HPPS from Malvern Instruments, UK at 22°C. The cumulative Z average diameter calculated from the measured autocorrelation function is reported (ISO standard 13321).

[0121] Aqueous dispersions of polymers P are generally polymers obtained by emulsion polymerization of ethylenically unsaturated monomers M, also referred to below as polymer emulsions. Polymer emulsions are well known to the person skilled in the art and are prepared, for example, by means of free-radically initiated aqueous emulsion polymerization of ethylenically unsaturated monomers M in the form of aqueous polymer dispersions. This technology has been described in detail in the art and is therefore familiar to those skilled in the art [see, for example, Encyclopedia of Polymer Science and Engineering, Vol. 8, pp. 659-677, John Wiley & Sons, Inc., 1987; DC Blackley, Emulsion Polymerisation, pp. 155-465, Applied Science Publishers, Ltd., Essex, 1975; DC Blackley, Polymer Latices, 2nd edition, Vol. 1, pp. 33-415, Chapman & Hall, 1997; H.Warson, The Applications of Synthetic Resin Emulsions, pp. 49-244, Ernest Benn, Ltd., London, 1972; J.Piirma, Emulsion Polymerisation, pp. 1-287, Academic Press, 1982; F. Dis-persionen synthetischer Hochpolymerer, pp. 1 to 160, Springer-Verlag, Berlin, 1969 and patent specification DE-A 40 03 422]. Free-radical initiated aqueous emulsion polymerization is usually carried out by dispersing the ethylenically unsaturated monomers in an aqueous medium, usually with the use of dispersing aids such as emulsifiers and / or protective colloids, and polymerizing them with the aid of at least one water-soluble free-radical polymerization initiator. The residual amount of unreacted ethylenically unsaturated monomers in the aqueous polymer dispersion obtained is usually reduced by chemical and / or physical techniques which are likewise known to the person skilled in the art [see, for example, EP-A 771 328, DE-A 196 24 299, DE-A 196 21 027,

[0122] DE-A 19741184, DE-A 19741187, DE-A 19805122, DE-A 19828183, DE-A 19839199, DE-A 19840586 and 19847115]; adjusting the polymer solids content to the desired level by dilution or concentration; or mixing the aqueous polymer dispersion with other conventional auxiliaries (e.g. bactericidal, foam-modifying or viscosity-modifying additives).

[0123] In addition to these so-called primary aqueous polymer dispersions, the person skilled in the art also knows so-called secondary aqueous polymer dispersions. These are to be understood as aqueous polymer dispersions, in the preparation of which the polymer is produced outside the aqueous dispersion medium, for example as a solution in a suitable non-aqueous solvent. This solution is subsequently transferred to the aqueous dispersion medium and the solvent is separated off in the case of dispersion, usually by distillation.

[0124] Preferably, the aqueous polymer dispersion of the polymer P is a predominantly aqueous polymer dispersion, in particular an aqueous polymer dispersion obtained by aqueous emulsion polymerization of ethylenically unsaturated monomers M.

[0125] Preferably, polymer P is a copolymer of ethylenically unsaturated monomers M. As used herein, the term copolymer refers to a polymer made from two or more (e.g. 2, 3, 4, 5 or 6 or more) different ethylenically unsaturated monomers M. Preferably, the copolymer comprises two ethylenically unsaturated comonomers having a relatively low solubility and a relatively high solubility in water, wherein the comonomer having a relatively low solubility preferably constitutes the main part of the polymer. Ethylenically unsaturated monomers with low water solubility are those whose solubility in water at 20°C and 1 bar does not exceed 50 g / l. These monomers are hereinafter referred to as monomers M1. Monomers with higher water solubility are those whose solubility in water at 20°C and 1 bar is at least 60 g / l. These monomers are hereinafter referred to as monomers M2.

[0126] Preferably, the polymer P consists of:

[0127] i) 80 to 99.9 pphm, more particularly 85 to 99.5 pphm, of at least one neutral, nonfunctional, monoethylenic monomer M.1, whose water solubility in deionized water at 20° C. and 1 bar does not exceed 50 g / l, for example in the range from 0.01 g / l to 50 g / l; and

[0128] ii) 0.1 pphm to 20 pphm, more particularly 0.5 pphm to 15 pphm, of at least one further ethylenically unsaturated monomer different from the monomer M1.

[0129] The term "pphm" means parts per hundred parts of monomer, and is an abbreviation of the term "weight % based on the total amount of monomers."

[0130] The term "neutral" means that the monomer has neither basic or acidic groups nor ionic groups.

[0131] The term "non-functional" means that the monomer has no functional group capable of polymer-analogous reaction, ie, bonding reaction with another group of the polymer or with a crosslinker or with an inorganic substance.

[0132] The term unsaturated monomer other than monomer M1 means

[0133] - monoethylenically unsaturated neutral monomers having a water solubility in deionized water of more than 50 g / l at 20° C. and 1 bar, for example at least 60 g / l at 20° C. and 1 bar;

[0134] - monoethylenically unsaturated monomers having a basic or acidic group or an ionic group, for example an acidic group such as a carboxyl group (COOH), a SO3H group, a PO3H2 or an O-PO3H2 group and their salts, a basic group such as a dialkylamino group, or an ionic group such as the corresponding anionic group of one of the abovementioned acidic groups, or a cationic group such as a quaternized amino group;

[0135] - monoethylenically unsaturated monomers having functional groups capable of polymer analog reaction, such as ketocarbonyl groups, aldehyde groups, isocyanate groups, 1,3-dicarbonyl groups, urea groups, N-alkylolamide groups or hydrolyzable silane groups; and

[0136] - Ethylenically unsaturated monomers having at least 2 ethylenically unsaturated double bonds.

[0137] Examples of neutral nonfunctional monoethylenically unsaturated monomers M.1 are:

[0138] - esters of acrylic acid and / or methacrylic acid with alkanols having 1 to 20 C atoms, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, 2-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, n-heptyl acrylate, n-octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate, 2-propylpentyl acrylate, n-decyl acrylate, 2-propylheptyl acrylate, C acrylate 10 Isoamyl branched alcohol esters, 1-propylheptyl acrylate, lauryl acrylate and stearyl acrylate. C1-C methacrylic acid 20 Examples of alkyl esters include, but are not limited to, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, 2-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, n-heptyl methacrylate, n-octyl methacrylate, 2-octyl methacrylate, 2-ethylhexyl methacrylate, 2-propylpentyl methacrylate, n-decyl methacrylate, 2-propylheptyl methacrylate, C-butyl methacrylate, 2-octyl methacrylate, 2-ethylhexyl methacrylate, 2-propylpentyl methacrylate, decyl methacrylate, 2-propylheptyl methacrylate, 2-octyl methacrylate, 2-octyl methacrylate, 2-ethylhexyl methacrylate, 2- 10 Isoamyl branched alcohol esters, 1-propylheptyl methacrylate, lauryl methacrylate, and stearyl methacrylate;

[0139] - esters of acrylic acid and / or methacrylic acid with cycloalkanols having 3 to 10 C atoms, in particular 5 to 10 C atoms, such as cyclopropyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, 4-methylcyclohexyl acrylate, 4-tert-butylcyclohexyl acrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, 4-methylcyclohexyl methacrylate and 4-tert-butylcyclohexyl methacrylate;

[0140] - esters of acrylic acid and / or methacrylic acid with heterocyclic alcohols, such as furfuryl acrylate and furfuryl methacrylate;

[0141] - vinylaromatic hydrocarbons, such as styrene, 2-methylstyrene, 4-methylstyrene, 2-n-butylstyrene, 4-n-butylstyrene or 4-n-decylstyrene;

[0142] - conjugated dienes, such as butadiene or isoprene;

[0143] - olefins and halogenated olefins, such as ethylene, propylene, vinyl chloride, vinylidene chloride;

[0144] -Saturated C1-C 12Vinyl and allyl esters of alkanoic acids, such as vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl octanoate, vinyl laurate, vinyl stearate, vinyl versatate, allyl formate, allyl acetate, allyl propionate, allyl butyrate or allyl laurate.

[0145] Preferred monomers M1 are esters of acrylic acid with alkanols having 1 to 10 C atoms; esters of methacrylic acid with alkanols having 1 to 10 C atoms; esters of acrylic acid with cycloalkanols having 5 to 10 C atoms; esters of methacrylic acid with cycloalkanols having 5 to 10 C atoms; furfuryl acrylate; furfuryl methacrylate; vinyl aromatic hydrocarbon compounds, in particular styrene; conjugated dienes, in particular butadiene; vinyl esters of saturated C1-C8 alkanoic acids, in particular vinyl acetate; and olefins, in particular ethylene; and combinations thereof.

[0146] Other ethylenically unsaturated monomers besides monomer M1 include, but are not limited to, monoethylenically unsaturated neutral monomers M2 having a solubility of at least 60 g / L in deionized water, such as

[0147] - primary amides of monoethylenically unsaturated monocarboxylic acids having 3 to 8 C atoms, such as acrylamide and methacrylamide, and

[0148] - esters of acrylic acid and / or methacrylic acid with alkanediols having 2 to 4 C atoms, such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxyethyl ethacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 3-hydroxybutyl acrylate, 3-hydroxybutyl methacrylate, 4-hydroxybutyl acrylate or 4-hydroxybutyl methacrylate;

[0149] The total amount of monomers M2, based on the total amount of monomers M, is preferably in the range of 0 to 15% by weight, in particular in the range of 0 to 10% by weight, for example in the range of 0.1 to 15% by weight, in particular in the range of 0.5 to 10% by weight.

[0150] Other ethylenically unsaturated monomers other than monomer M1 include, but are not limited to, monoethylenically unsaturated monomers M3 having at least one acidic group or a group such as a carboxyl group (COOH), a SO3H group, a PO3H2 group or an O-PO3H2 group, and salts thereof, such as sodium salts, potassium salts or ammonium salts thereof. Specific groups of such monomers include:

[0151] - monoethylenically unsaturated monomers with 1 or 2 COOH groups (monomers M3a), for example monocarboxylic acids having 3 to 8 C atoms and monoethylenically unsaturated dicarboxylic acids having 4 to 8 C atoms, such as acrylic acid, methacrylic acid, itaconic acid and citraconic acid, particular preference being given to methacrylic acid;

[0152] - monoethylenically unsaturated sulfonic acids (monomer M3b) and their salts, such as vinylsulfonic acid, allylsulfonic acid, sulfoethyl acrylate, sulfoethyl methacrylate, sulfopropyl acrylate, sulfopropyl methacrylate, 2-hydroxy-3-acryloxypropylsulfonic acid, 2-hydroxy-3-methacryloxypropylsulfonic acid, styrenesulfonic acid and 2-acrylamido-2-methylpropanesulfonic acid, especially their salts, more especially their sodium, potassium or ammonium salts;

[0153] - monoethylenically unsaturated monomers with O-PO3H2 groups (phosphate groups - monomers M3c) and their salts, in particular their sodium, potassium or ammonium salts, for example monomers of formula (M3c-I)

[0154] H2C=C(R)-C(=O)-OA-[O-Alk] n -OP(=O)(OH)2(M3c-I)

[0155] in

[0156] A is C2-C4-alkanediyl, in particular 1,2-ethanediyl, 1,3-propylenediyl or 1,2-propylenediyl,

[0157] Repeating unit [Alk-O] n The Alk in each of the groups are the same or different and are 1,2-ethanediyl or 1,2-propylenediyl,

[0158] n is an integer from 0 or 1 to 20, in particular an integer from 0 or 1 to 10, and

[0159] R is hydrogen or methyl,

[0160] Examples of monomer M3c are mono(meth)acryloyloxyethyl phosphate, mono(meth)acryloyloxypropyl phosphate, mono(meth)acryloyl(oxy-1,2-ethanediyl) 1-20 Phosphate and mono(meth)acryloyl(oxy-1,2-propanediyl) 1-20 Phosphoric acid esters and their salts, in particular their sodium, potassium or ammonium salts.

[0161] Preferably, the polymer P contains not more than 2 pphm of monoethylenically unsaturated monomers M3. Preferably, the total amount of monomers M3 will be at most 2 pphm, such as from 0.1 pphm to 2 pphm, or at most 1.5 pphm, such as from 0.2 pphm to 1.5 pphm.

[0162] Specifically, the polymer of polymer P contains at most 1.5pphm, for example 0.1pphm to 1.5pphm, of one or more monomers M3a having a carboxylic acid group, such as acrylic acid, methacrylic acid or itaconic acid, particularly preferably methacrylic acid. Preferably, the polymer contains at most 1pphm, for example 0.01pphm to 1.0pphm, of one or more monomers M3b having a sulfonic acid group. Preferably, the polymer contains at most 1pphm, for example 0.01pphm to 1.0pphm, of one or more monomers M3b. Preferably, the polymer contains at most 1.5pphm, for example 0.1pphm to 1.5pphm, of one or more monomers M3c. Preferably, the total amount of monomer M3 will be at most 2pphm, for example 0.1pphm to 2pphm, or at most 1.5pphm, for example 0.2pphm to 1.5pphm.

[0163] The total amount of monomers M2+M3, based on the total amount of monomers M, is preferably in the range from 0.1% to 15% by weight, in particular in the range from 0.2% to 10% by weight.

[0164] In addition to the above-mentioned monoethylenically unsaturated monomers M1 and optional monomers M2 and / or M3, the monomers M may also contain small amounts of monoethylenically unsaturated monomers M4 having one unsaturated double bond and another reactive group susceptible to post-crosslinking reactions, including

[0165] - monoethylenically unsaturated monomers containing keto groups (monomers M4a), for example acetoacetoxyethyl acrylate, acetoacetoxypropyl methacrylate, acetoacetoxybutyl methacrylate, acetoacetoxyethyl methacrylate, diacetone acrylamide (DAAM) and diacetone methacrylamide;

[0166] - monoethylenically unsaturated monomers carrying one or more urea groups (monomer M4b), such as 2-(2-oxoimidazolidin-1-yl)ethyl (meth)acrylate, 2-ureido (meth)acrylate, N-[2-(2-oxo-oxazolidin-3-yl)ethyl]methacrylate;

[0167] - monoethylenically unsaturated monomers carrying epoxy groups (monomer M4c), such as monoglycidyl allyl ether, glycidyl acrylate, glycidyl methacrylate, 2-glycidyloxyethyl acrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl acrylate, 3-glycidyloxypropyl methacrylate, 4-glycidyloxybutyl acrylate, 4-glycidyloxybutyl methacrylate, 3,4-epoxybutyl acrylate, 3,4-epoxybutyl methacrylate, 4,5-epoxypentan-2-yl acrylate or 4,5-epoxypentan-2-yl methacrylate, preferably epoxy-functional (meth)acrylate monomers;

[0168] N-Hydroxyalkylamides of α,β-monoethylenically unsaturated carboxylic acids having 3 to 10 carbon atoms and their esters with alcohols having 1 to 4 carbon atoms, for example N-methylolacrylamide and N-methylolmethacrylamide (monomers M4d).

[0169] Among the above-mentioned monomers M4, preferred are monomers M4a and M4c.

[0170] The total amount of monomers M4, based on the total amount of monomers M, is preferably in the range from 0% to 5% by weight, for example in the range from 0.1% to 5.0% by weight, in particular in the range from 0.2% to 4.0% by weight.

[0171] In addition to the above-mentioned monoethylenically unsaturated monomer M1 and optional monomers M2, M3 and / or M4, monomer M may also contain a small amount of monoethylenically unsaturated monomer M5 with an unsaturated double bond and a hydrolyzable silane group. In the context of the present invention, a hydrolyzable silane group refers to a silane group with 1, 2 or 3 groups, which are cleaved from a silicon atom in the presence of water to form a Si-OH group. Typically, these groups are O-bound, such as alkoxy, cycloalkoxy or phenoxy. The hydrolyzable silane group is typically bound to the carbon atom of the monomer. Specifically, the silicon atom of the hydrolyzable silane group carries n alkoxy groups and n-3 alkyl groups, n being 1, 2 or 3, wherein the above-mentioned groups are bound to the silicon atom. In this article, the alkoxy group is preferably selected from C1-C4-alkoxy, particularly selected from methoxy and ethoxy, and the alkyl moiety is preferably selected from C1-C4-alkyl, such as methyl or ethyl. The hydrolyzable silane groups of suitable monomers M2 are preferably trialkoxysilane groups (n=3) or alkyldialkoxysilane groups (n=2), wherein the alkoxy moieties of the trialkoxysilane groups or alkyldialkoxysilane groups are preferably selected independently of one another from C1-C4-alkoxy groups, in particular from methoxy and ethoxy groups, while the alkyl moieties of the alkyldialkoxysilane groups are preferably selected from C1-C4-alkyl groups, in particular from methyl and ethyl groups. Particular preference is given to monomers M2 which carry trialkoxysilane groups or alkyldialkoxysilane groups, wherein in each case all alkoxy moieties are identical and selected from C1-C4-alkoxy groups, in particular methoxy and ethoxy groups, while the alkyl moieties of the alkyldialkoxysilane groups are C1-C4-alkyl groups, in particular methyl or ethyl groups.

[0172] Preferred monomers M5 are selected from the group consisting of vinyltrialkoxysilanes, such as in particular vinyltrimethoxysilane or vinyltriethoxysilane; alkylvinyldialkoxysilanes, such as in particular methylvinyldimethoxysilane, methylvinyldiethoxysilane or ethylvinyldiethoxysilane; acryloxyalkyltrialkoxysilanes, such as in particular acryloxyethyltrimethoxysilane, acryloxyethyltriethoxysilane, acryloxypropyltrimethoxysilane or acryloxypropyltriethoxysilane; methacryloxyalkyltrialkoxysilanes, such as in particular methacryloxyethyltrimethoxysilane, methacryloxyethyltriethoxysilane, triethoxysilane, methacryloxypropyltrimethoxysilane or methacryloxypropyltriethoxysilane; acryloxyalkyl-alkyldialkoxysilanes, such as in particular acryloxyethyl-methyldimethoxysilane, acryloxyethyl-methyldiethoxysilane, acryloxypropyl-methyldimethoxysilane or acryloxypropyl-methyldiethoxysilane; and methacryloxyalkyltrialkoxysilanes, such as in particular methacryloxyethyl-methyldimethoxysilane, methacryloxyethyl-methyldiethoxysilane, methacryloxypropyl-methyldimethoxysilane or methacryloxypropyl-methyldiethoxysilane.

[0173] Particularly preferred are monomers M5 selected from the group consisting of vinyltrialkoxysilanes, such as in particular vinyltrimethoxysilane or vinyltriethoxysilane; acryloxyalkyltrialkoxysilanes, such as in particular acryloxyethyltrimethoxysilane, acryloxyethyltriethoxysilane, acryloxypropyltrimethoxysilane or acryloxypropyltriethoxysilane; and methacryloxyalkyltrialkoxysilanes, such as in particular methacryloxyethyltrimethoxysilane, methacryloxyethyltriethoxysilane, methacryloxypropyltrimethoxysilane or methacryloxypropyltriethoxysilane.

[0174] In a particularly preferred embodiment of the invention, the monomer M5 is selected from vinyltrialkoxysilanes, such as in particular vinyltrimethoxysilane or vinyltriethoxysilane, and methacryloxyalkyltrialkoxysilanes, in particular methacryloxypropyltrimethoxysilane.

[0175] The total amount of monomers M5 will usually not exceed 1 pphm and, if present, will typically range from 0.01 to 1 pphm, preferably from 0.03 to 0.7 pphm, more preferably from 0.05 to 0.5 pphm, particularly from 0.07 to 0.4 pphm, in particular from 0.1 to 0.3 pphm.

[0176] In addition to the above-mentioned monoethylenically unsaturated monomers M1, M2, M3, M4 and M5, the monomers M may also contain a small amount of ethylenically unsaturated monomers M6 with at least 2, for example 2 to 6, non-conjugated ethylenically unsaturated double bonds. These monomers will lead to crosslinking of the polymer chains during polymerization and are therefore referred to as crosslinking monomers M6. Exemplary crosslinking monomers include divinylbenzene, diesters or triesters of diols and triols with monoethylenically unsaturated C3-C6 monocarboxylic acids, such as di(meth)acrylates, tri(meth)acrylates and tetra(meth)acrylates, such as alkylene glycol diacrylates and dimethacrylates, such as ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate and propylene glycol diacrylate, trimethylolpropane triacrylate and trimethacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate, and vinyl esters and allyl esters of ethylenically unsaturated acids, such as vinyl methacrylate, vinyl acrylate, allyl methacrylate, allyl acrylate, and divinyl esters and diallyl esters of dicarboxylic acids, such as diallyl maleate and diallyl fumarate and methylenebisacrylamide. The amount of the monomer M3 will generally not exceed 2 pphm, and in particular be less than 1 pphm.

[0177] More preferably, the polymer P is at least one monovinyl aromatic monomer M1a and at least one C1-C12 selected from conjugated aliphatic dienes, acrylic acid, 10 -alkyl esters, C1-C 10 -alkyl esters, acrylic acid, C5-C 10 -Cycloalkyl esters and methacrylic acid C5-C 10 - Copolymers of further monomers M1b of cycloalkyl esters and mixtures thereof, optionally one or more further comonomers M2 and optionally one or more further comonomers M3, M4, M5 and / or M6.

[0178] The monovinylaromatic monomer M1a is preferably styrene.

[0179] Monomer M1b is preferably selected from conjugated aliphatic dienes, especially butadiene; C1-C 10 -alkyl esters, hereinafter referred to as C1-C 10 -alkyl acrylate; and C1-C 10 -alkyl esters, hereinafter referred to as C1-C 10 -alkyl methacrylate. Specifically, M1b is selected from butadiene, acrylic acid C1-C 10 -alkyl esters, methacrylate C1-C4-alkyl esters. 10Examples of C1-C4-alkyl esters are methyl methacrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-butyl acrylate, tert-butyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate and 2-propyl-heptyl acrylate. Among them, n-butyl acrylate, isobutyl acrylate, 2-octyl acrylate and 2-ethylhexyl acrylate are preferred. Examples of C1-C4-alkyl methacrylates are methyl methacrylate, ethyl methacrylate, tert-butyl methacrylate and n-butyl methacrylate.

[0180] In this context, the polymer P, in which the monomer M1a is styrene and the further monomers M1b are selected from alkyl esters (especially C1-C1 10 -alkyl esters) and cycloalkyl esters (especially C5-C 10 -cycloalkyl esters) and their mixtures are called styrene-acrylate copolymers. Styrene acrylate copolymers may contain one or more polymerized monomers M2, M3, M4, M5 and / or M6.

[0181] In this context, polymers P, in which monomer M1a is styrene and the further monomer M1b comprises butadiene or is butadiene, are referred to as styrene-butadiene copolymers. The styrene butadiene copolymers in these dispersions may contain one or more polymerized monomers M2, M3, M4, M5 and / or M6.

[0182] Likewise suitable are polymers P in which the monomers M1 comprise vinyl acetate, in particular a combination of vinyl acetate and at least one C2-C6-monoolefin, such as ethylene, or a combination of vinyl acetate, at least one C2-C6-monoolefin, such as ethylene, and a further monomer M1b as defined above, the further monomer being preferably selected from the group consisting of C2-C6-monoolefins. 12 Vinyl esters of alkanoic acids, especially branched C4-C 12 Alkanoic acid (e.g., Koch acid, such as pivalic acid or vinyl esters of acrylic acid, such as Hexion's VeoVa 9 vinyl ester, VeoVa 10 vinyl ester, and VeoVa EH vinyl ester, C2-C 10 -alkyl esters, C1-C 10 -alkyl esters, acrylic acid, C5-C 10 -Cycloalkyl esters and methacrylic acid C5-C 10 - Cycloalkyl esters and mixtures thereof. In the following, polymers P in which monomers M1 comprise a combination of vinyl acetate, ethylene and optionally further monomers M1b as defined above are also referred to as ethylene-vinyl acetate copolymers or EVA copolymers, respectively.

[0183] Likewise suitable are polymers P analogous to styrene acrylates in which at least a portion of the styrene is replaced by acrylonitrile. In these polymers P, the monomers M comprise acrylonitrile and optionally styrene as monomers M1a" and at least one further monomer M1b" selected from the group consisting of C1-C 10 -alkyl esters, C1-C 10 -alkyl esters, acrylic acid, C5-C 10 -Cycloalkyl esters and methacrylic acid C5-C 10 -cycloalkyl esters and mixtures thereof), optionally one or more further comonomers M2 and optionally one or more further comonomers M3 and / or M4. These polymers P are referred to herein as acrylonitrile-acrylate copolymers.

[0184] Likewise suitable are all acrylic polymers. In these polymers P, the monomers M comprise as monomers M1a' at least one C1-C4-alkyl ester, in particular methyl methacrylate, and at least one further monomer M1b' selected from the C1-C4-alkyl groups of acrylic acid. 10 -alkyl esters, C5-C 10 -alkyl esters, acrylic acid, C5-C 10 -Cycloalkyl esters and methacrylic acid C5-C 10 -cycloalkyl esters and mixtures thereof), optionally one or more further comonomers M2 and optionally one or more further comonomers M3, M4, M5 and / or M6.

[0185] Even more preferably, the polymer P is selected from

[0186] a vinyl aromatic compound M1a (especially styrene) and at least one selected from the group consisting of conjugated aliphatic dienes, alkyl esters (especially C1-C 10 -alkyl esters), alkyl esters (especially C1-C 10 -alkyl esters), cycloalkyl esters (especially C5-C 10 -cycloalkyl esters) and cycloalkyl esters (especially C5-C 10 -cycloalkyl esters) and mixtures thereof, such as styrene-butadiene copolymers or styrene-acrylate copolymers;

[0187] - and copolymers of vinyl esters and α-olefins, such as ethylene, for example ethylene-vinyl acetate copolymers.

[0188] Here and below, the term "copolymer" refers to a polymer containing at least two different types of polymerized monomers. Thus, the term "copolymer" includes polymers made from two different types of monomers and polymers made from three or more different types of monomers (terpolymers, etc.).

[0189] Specifically, the polymer P is selected from styrene-acrylate copolymers, styrene-butadiene copolymers, all-acrylic acid copolymers, acrylonitrile-acrylate copolymers, vinyl acetate polymers and ethylene-vinyl acetate copolymers, and styrene-acrylate copolymers and styrene-butadiene copolymers are particularly preferred.

[0190] In a more preferred set of embodiments, the monomers M forming the polymer P comprise:

[0191] i. 80% to 99.9% by weight, in particular 85% to 99.5% by weight, based on the total amount of monomers M, of at least one monomer M1 selected from the combination of at least one monovinylaromatic monomer M1a and at least one further monomer M1b selected from conjugated aliphatic dienes, alkyl esters (in particular C1-C12 of acrylic acid and / or methacrylic acid), 10 -alkyl esters) and cycloalkyl esters (especially C5-C 10 -cycloalkyl esters) and mixtures thereof;

[0192] ii. 0 to 15% by weight, in particular 0 to 10% by weight, for example 0.1 to 15% by weight or 0.5 to 10% by weight, based on the total amount of monomers M, of one or more monomers M2, the one or more monomers being selected from monoethylenically unsaturated neutral monomers having a solubility in water at 20° C. of at least 60 g / L;

[0193] iii. 0 to 2.0% by weight, in particular 0 to 1.5% by weight, for example 0.1 to 2.0% by weight or 0.2 to 1.5% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M3 having at least one acid group;

[0194] iv. 0 to 5% by weight, for example 0.1 to 5.0% by weight, in particular 0.2 to 4.0% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M4, which influence the self-crosslinking of the polymer;

[0195] v. 0 to 1.0% by weight, for example 0.01 to 1.0% by weight, in particular 0.03 to 0.7% by weight or 0.05 to 0.5% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M5 having hydrolyzable silane groups, in particular selected from vinyltrialkoxysilanes, such as vinyltrimethoxysilane or vinyltriethoxysilane, and methacryloxyalkyltrialkoxysilanes, in particular methacryloxypropyltrimethoxysilane;

[0196] The total amount of monomers M2, M3, M4 and M5, based on the total amount of monomers M, is in the range of 0.1% to 20% by weight, in particular in the range of 0.2% to 15% by weight, and the total amount of monomers M2 and M3, based on the total amount of monomers M, is preferably up to 15% by weight, in particular up to 10% by weight.

[0197] In this group of more preferred embodiments, monomer M2 is as defined above and is preferably selected from the primary amides of monoethylenically unsaturated monocarboxylic acids having 3 to 8 C atoms, such as acrylamide and methacrylamide, and esters of acrylic acid and / or methacrylic acid with alkanediols having 2 to 4 C atoms, such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 3-hydroxybutyl acrylate, 3-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate or 4-hydroxybutyl methacrylate. More preferably, M2 is selected from the esters of acrylamide, methacrylamide and methacrylic acid with alkanediols having 2 to 4 C atoms, such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 3-hydroxybutyl methacrylate or 4-hydroxybutyl methacrylate. Specifically, M2 is selected from the group consisting of acrylamide, methacrylamide, 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate.

[0198] In this group of more preferred embodiments, the monomer M3 is as defined above and is preferably selected from methacrylic acid, 2-hydroxy-3-acryloxypropylsulfonic acid, 2-hydroxy-3-methacryloxypropylsulfonic acid, styrenesulfonic acid and 2-acrylamido-2-methylpropanesulfonic acid and their salts, in particular their sodium, potassium or ammonium salts, and monomers of formula M3c-I, such as mono(meth)acryloxyethyl phosphate, mono(meth)acryloxypropyl phosphate, mono(meth)acryloyl(oxy-1,2-ethanediyl) 1-20 Phosphate and mono(meth)acryloyl(oxy-1,2-propanediyl) 1-20 Phosphoric acid esters and their salts, in particular their sodium, potassium or ammonium salts.

[0199] In this group of more preferred embodiments, monomer M4 is as defined above and is preferably selected from the group consisting of monomers M4a and M4c, particularly preferred are monomers M4a with a 1,3-dicarbonyl moiety, such as acetoacetoxyethyl acrylate, acetoacetoxypropyl methacrylate, acetoacetoxybutyl methacrylate, acetoacetoxyethyl methacrylate, and epoxy-functionalized (meth)acrylate monomers, such as glycidyl acrylate, glycidyl methacrylate, 2-glycidyloxyethyl acrylate, 2-glycidyloxyethyl methacrylate, 3-glycidyloxypropyl acrylate, and 3-glycidyloxypropyl methacrylate.

[0200] In a particular set of embodiments, the monomers M forming the polymer P comprise:

[0201] i. 80% to 99.9% by weight, in particular 85% to 99.5% by weight, based on the total amount of monomers M, of at least one monomer M1 selected from the combination of styrene and at least one further monomer M1b selected from butadiene and alkyl esters, in particular C1-C1 acrylic acid. 10 - alkyl esters;

[0202] ii. 0.1 to 15% by weight, in particular 0.5 to 10% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from acrylamide, methacrylamide and esters of methacrylic acid with alkanediols having 2 to 4 C atoms;

[0203] iii. optionally 0 to 2.0% by weight, in particular 0 to 1.5% by weight, for example 0.1 to 2.0% by weight or 0.2 to 1.5% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M3 having at least one acid group, in particular selected from the monomers methacrylic acid and monomers M3c and combinations thereof;

[0204] iv. optionally 0 to 5% by weight, for example 0.1 to 5.0% by weight, in particular 0.2 to 4.0% by weight, based on the total amount of monomers M, of one or more monomers M4 listed above, in particular selected from monomers M4a and M4c; and

[0205] v. Optionally, based on the total amount of monomers M, 0 to 1 wt. %, for example 0.01 to 1.0 wt. %, in particular 0.03 to 0.7 wt. % or 0.05 to 0.5 wt. %, of one or more monoethylenically unsaturated monomers M5 having hydrolyzable silane groups, in particular selected from vinyltrialkoxysilanes, such as vinyltrimethoxysilane or vinyltriethoxysilane, and methacryloxyalkyltrialkoxysilanes, in particular methacryloxypropyltrimethoxysilane.

[0206] In another specific group of embodiments, the monomers M forming the polymer P comprise:

[0207] i. 80% to 99.9% by weight, in particular 85% to 99.5% by weight, based on the total amount of monomers M, of at least one monomer M1 selected from the combination of styrene and at least one further monomer M1b selected from butadiene and alkyl esters, in particular C1-C1 acrylic acid. 10 - alkyl esters;

[0208] ii. optionally 0 to 10% by weight, for example 0.1 to 5% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from acrylamide, methacrylamide and esters of methacrylic acid with alkanediols having 2 to 4 C atoms;

[0209] iii. 0.1% to 1.5% by weight, in particular 0.2% by weight, based on the total amount of monomers M

[0210] to 1.0% by weight of one or more monoethylenically unsaturated monomers M3 having at least one acid group, in particular chosen from the monomers methacrylic acid and monomers M3c and combinations thereof;

[0211] iv. optionally 0% to 5% by weight, for example 0.1% by weight, based on the total amount of monomers M

[0212] % to 5.0% by weight, in particular 0.2% to 4.0% by weight, of one or more monomers M4 listed above, in particular selected from monomers M4a and M4c; and

[0213] v. Optionally, based on the total amount of monomers M, 0 to 1 wt. %, for example 0.01 to 1.0 wt. %, in particular 0.03 to 0.7 wt. % or 0.05 to 0.5 wt. %, of one or more monoethylenically unsaturated monomers M5 having hydrolyzable silane groups, in particular selected from vinyltrialkoxysilanes, such as vinyltrimethoxysilane or vinyltriethoxysilane, and methacryloxyalkyltrialkoxysilanes, in particular methacryloxypropyltrimethoxysilane.

[0214] The monomers M forming the polymer P may be of petrochemical origin or may be of biorenewable origin. In particular, at least 30% by weight of the monomers M, preferably at least 40% by weight or at least 50% by weight of the monomers M are based on biorenewable origin, which means that their biogenic carbon content, based on the total amount of carbon in the monomers from biorenewable origin, is at least 30 mol %, in particular at least 40 mol %.

[0215] The term "biochar" means that the carbon is of biological origin and comes from biological material / renewable resources. The content in biochar and the content in biomaterial are expressions indicating the same value. A material of renewable origin or biomaterial is an organic material in which the carbon comes from CO2 that has been recently fixed (on a human scale) from the atmosphere by photosynthesis. Biomaterial (100% carbon of natural origin) has a carbon content greater than 10 -12 , usually about 1.2×10 -12 of 14 C / 12 C isotope ratio, while fossil materials have a ratio of 0. In practice, on time scales of at most a few decades, the isotopes 14 C is formed in the atmosphere and subsequently incorporated via photosynthesis. 14 The half-life of C is 5,730 years. Therefore, materials from photosynthesis, usually plants, must have the highest content of the isotope. 14 C. The determination of the content of biomass or biochar can be carried out according to standards ASTM D 6866-12, method B (ASTM D 6866-06) and ASTM D 7026 (ASTM D 7026-04).

[0216] The term "biorenewable source" refers to organic materials in which the carbon comes from a non-fossil biological source. Examples of biorenewable sources include, but are not limited to, sugars such as glucose or sucrose; and starch obtained from plants such as corn, corn, sugar cane, sugar beets, potatoes, sweet potatoes or cassava; other polysaccharides of plant origin, such as cellulose, lignocellulose, hemicellulose, pectin, chitin, fructan and pullulan; vegetable oils; biomass obtained from plant or agricultural waste, etc.

[0217] Monomers and monomer precursors, such as alcohols and fatty acids, can be produced directly from such biological resources via biological processes including fermentation and the like.

[0218] The example of monomers and monomer precursors that can be directly obtained from bio-renewable sources is acrylic acid, methacrylic acid, itaconic acid, alkyl esters and cycloalkyl esters of acrylic acid and methacrylic acid, wherein at least the carbon atoms of the alkyl and cycloalkyl groups are respectively of biological origin, i.e., they are at least partially composed of bio-carbon. Specifically, the corresponding alkanols and cycloalkanols for preparing the alkyl esters and cycloalkyl esters of acrylic acid and methacrylic acid, respectively, preferably have a bio-carbon content of at least 70 mol % based on the total amount of carbon atoms in the corresponding monomers. This content is advantageously higher, particularly greater than or equal to 80 mol %, preferably greater than or equal to 90 mol % and advantageously equal to 100 mol %. Similarly, itaconic acid, citraconic acid and mesaconic acid can be produced on a large scale by renewable materials, for example, by fermentation of raw materials containing glucose, sucrose, starch or cellulose. Similarly, acrylic acid and methacrylic acid can be produced by bio-renewable sources. Another example is the vinyl ester of alkanoic acid, wherein at least alkanoic acid is produced by bio-renewable sources.

[0219] It is also possible to produce isotope-enriched 14 Here, biomass or organic waste of natural origin (e.g. agricultural waste) is converted into methane or unsaturated hydrocarbons (naphtha) via fermentation or abiotic classical chemical processes. The methane and / or unsaturated hydrocarbons thus obtained, optionally combined with methane and / or unsaturated hydrocarbons of petrochemical origin, are converted by abiotic conventional chemical methods into products having a relative carbon content greater than zero, e.g. >5×10 -14 The isotope ratio 14 C / 12 C monomer or monomer precursor.

[0220] In the aqueous composition (II), the polymer content is preferably 20 to 65% by weight, more preferably 30 to 60% by weight, in particular 35 to 55% by weight, based on the total weight of the aqueous composition (II).

[0221] Aqueous polymer dispersions of polymers P, in particular aqueous polymer dispersions of styrene-butadiene copolymers, aqueous polymer dispersions of styrene-acrylate copolymers, aqueous polymer dispersions of all-acrylic acid copolymers, aqueous polymer dispersions of acrylonitrile-acrylate copolymers and aqueous polymer dispersions of vinyl acetate homopolymers and copolymers, usually contain at least one surface-active compound. The surface-active compound serves to stabilize the aqueous dispersion of polymer P by keeping the particles of polymer P dispersed. The surface-active compound can be an emulsifier, a protective colloid or a mixture of both. Emulsifiers and protective colloids differ from one another in that their weight-average molar mass M w Emulsifiers usually have a weight average molar mass M of generally less than 2000. w , and the weight-average molar mass of the protective colloid M wIt can be up to 50 000, in particular above 2000 up to 50 000. Typically, the amount of surface-active compound is in the range from 0.1 to 10% by weight, in particular in the range from 0.5 to 5% by weight, based on the total amount of polymer in the aqueous polymer dispersion.

[0222] Preferably, the surface-active compound comprises one or more emulsifiers. The emulsifier is nonionic, anionic or cationic. In the case of using a mixture of emulsifiers, their compatibility must be ensured, which can be assessed by preliminary tests when uncertain. Typically, anionic emulsifiers are compatible with another anionic emulsifier or a nonionic emulsifier. Similarly, cationic emulsifiers are usually compatible with another cationic emulsifier or a nonionic emulsifier. Preferably, the emulsifier is an anionic emulsifier, a combination of two or more anionic emulsifiers or a combination of at least one anionic emulsifier and at least one nonionic emulsifier.

[0223] The nonionic emulsifier is, for example, an ethoxylated C8-C16-hydroxyethyl ester having a degree of ethoxylation of 3 to 50 (=ethylene oxide units [EO]: 3-50). 36 Fatty alcohols and ethoxylated mono-, di- and tri-C4-C 12 Examples of conventional nonionic emulsifiers are Emulgin B grade (cetyl alcohol / stearyl alcohol ethoxylates, RTM BASF), Dehydrol LS grade (fatty alcohol ethoxylates, EO units: 1-10, RTM BASF), Lutensol A grade (C 12 C 14 - Fatty alcohol ethoxylates, EO units: 3-8, RTM BASF), Lutensol AO grade (C 13 C 15 -oxyalcohol ethoxylates, EO units: 3-30), Lutensol AT grade (C 16 C 18 - fatty alcohol ethoxylates, EO units: 11-80), Lutensol ON grade (C 10 -oxyalcohol ethoxylates, EO units: 3-11) and Lutensol TO grades (C 13 -oxyalcohol ethoxylate, EO units: 3-20). Here and hereinafter, the phrase "EO units" means the average number of ethylene oxide repeating units in the emulsifier.

[0224] Anionic emulsifiers include, for example, alkali metal salts of dialkyl sulfosuccinates, C8-C 12 Alkali metal and ammonium salts of alkyl sulfates, C 12 -C 18 Alkali metal and ammonium salts of alkylsulfonic acids, C9-C18 Alkali metal and ammonium salts of alkylarylsulfonic acids, ethoxylated C 12 -C 18 Sulfate monoesters of alkanols (EO units: 4-30) or ethoxylated (C4-C 12 Alkali metal salts and ammonium salts of sulfuric acid monoesters of 2-(4-(2-(4-(2-alkyl)phenol) (EO units: 3-50). As additional anionic emulsifiers, compounds of the general formula I may also be used.

[0225]

[0226] Where R a and R b Each is a H atom or C4-C 24 -alkyl and not all H atoms, and M1 + and M2 + It can be an alkali metal ion and / or ammonium. a and R b Preferably, it is a straight-chain or branched alkyl group having 6 to 18 carbon atoms, in particular 6, 12 or 16 carbon atoms, or a hydrogen atom, wherein R a and R b M1 is not always hydrogen. + and M2 + Preferably sodium, potassium or ammonium, particularly preferably sodium. Particularly advantageous are compounds of the general formula I in which M1 + and M2 + All are sodium, R a is a branched alkyl group having 12 carbon atoms, and R b is hydrogen or R a Typically, technical mixtures are used which have a proportion of 50 to 90% by weight of monoalkylated products, for example 2A1 (RTM, Dow Chemical Corp.). The compounds of the general formula I are generally known, for example from US Pat. No. 4,269,749, and are commercially available. Further anionic emulsifiers are fatty alcohol phosphates, alkylphenol phosphates, alkyl polyglycol ether phosphates, alkyl polyoxyalkylene phosphates and fatty alcohol ether phosphates and their salts, in particular their alkali metal salts and ammonium salts, particularly preferably the alkali metal salts, such as the sodium salts.

[0227] A comprehensive description of suitable emulsifiers can be found in Houben-Weyl, Methoden der organ-ischen Chemie, Volume XIV / 1, Makromolekulare Stoffe, Georg-Thieme-Verlag, Stuttgart, 1961, pages 192 to 208.

[0228] As with the above-mentioned emulsifiers, suitable protective colloids may be nonionic, anionic or cationic. Examples of protective colloids are poly(vinyl alcohol), poly(alkylene glycol), poly(acrylic acid) and its alkali metal salts, poly(methacrylic acid) and its alkali metal salts and gelatin derivatives. Anionic protective colloids may also be copolymers containing a suitable amount of at least one anionic monomer in polymerized form, such as acrylic acid, methacrylic acid, maleic acid, 2-acrylamido-2-methylpropanesulfonic acid, p-vinylphenylsulfonic acid or their salt forms, preferably their alkali metal salts. Examples of cationic protective colloids are homopolymers and copolymers containing sufficient amounts of cationic monomers, in particular monoethylenically unsaturated monomers having one or more N-protonated or N-alkylated amino groups. Examples include N-protonated and N-alkylated derivatives of homopolymers or copolymers of N-vinylformamide in at least partially hydrolyzed form, N-protonated and N-alkylated derivatives of homopolymers or copolymers of N-vinylacetamide in at least partially hydrolyzed form, N-protonated and N-alkylated derivatives of homopolymers or copolymers of N-vinylcarbazole, N-protonated and N-alkylated derivatives of homopolymers or copolymers of 1-vinylimidazole, N-protonated and N-alkylated derivatives of homopolymers or copolymers of 2-vinylimidazole, 2- N-protonated and N-alkylated derivatives of homo- or copolymers of vinylpyridine, N-protonated and N-alkylated derivatives of homo- or copolymers of 4-vinylpyridine, N-protonated and N-alkylated derivatives of homo- or copolymers of acrylates carrying amine groups, N-protonated and N-alkylated derivatives of homo- or copolymers of methacrylates carrying amine groups, wherein the nitrogen of the amine group is protonated or permanently positively charged, for example by alkylation, at a pH below 7. Further comonomers in such cationic protective colloids may be acrylamide, methacrylamide and N-vinylpyrrolidone.

[0229] Protective colloids differ from polymers dispersed in aqueous polymer dispersions in that they are water-soluble or water-dispersible. The term "water-soluble or water-dispersible" is understood to mean that the corresponding protective colloid can be dissolved or dispersed in deionized water at 20° C. and 1013 mbar in an amount of at least 10 g / L of polymer, so that the resulting aqueous solution has no measurable particle size or has a particle size of at most 20 nm as determined by dynamic light scattering according to DIN 22412:2008.

[0230] A comprehensive description of suitable protective colloids can be found in Houben-Weyl, Methoden der organischen Chemie, Volume XIV / 1, Makromolekulare Stoffe, Georg-Thieme-Verlag, Stuttgart, 1961, pages 411 to 420.

[0231] The composition of the invention contains the polymer in powder form or in dispersion form in such an amount that the weight ratio of polymer to powder composition A is in the range from 1:10 to 1:1, in particular in the range from 1:5 to 1:1.

[0232] Furthermore, the compositions of the present invention may contain further adjuvants, such as

[0233] - wetting agents or dispersants,

[0234] - thickeners,

[0235] - flow control agents,

[0236] - biocides, and

[0237] -Defoaming agents.

[0238] If the composition according to the invention is formulated as a 2K formulation, the auxiliaries are usually incorporated into composition (II). However, flow control agents and defoamers can also be incorporated into composition (I).

[0239] Suitable wetting agents or dispersants are, for example, sodium, potassium or ammonium polyphosphates, alkali metal and ammonium salts of acrylic acid or maleic anhydride polymers, polyphosphonates (such as sodium 1-hydroxyethane-1,1-diphosphonate) and salts of naphthalenesulfonic acid, more particularly their sodium salts. Among the above dispersants, preferred are polymeric dispersants, such as alkali metal and ammonium salts of acrylic acid or maleic anhydride polymers. In particular, metal salts of polyacrylic acid are used.

[0240] Preferably, the content of the polymer dispersant is 0.1% to 2% by weight, in particular 0.1% to 1% by weight, based on the total weight of the polymer of composition (II).

[0241] Suitable thickeners are, for example, associative thickeners, such as polyurethane thickeners.

[0242] Suitable defoamers are, for example, silicone defoamers and magnesium stearate. Preferably, the defoamer is present in an amount of 0.05% to 2% by weight, in particular 0.1% to 1% by weight, based on the total weight of the polymer of composition (II).

[0243] In case the polymer P is used as the aqueous polymer dispersion, it is advantageous to keep the solid components A, B, C and optionally E and F physically separated from the polymer P in order to prevent the components A, B, C and optionally E and F from solidifying due to the presence of water in the aqueous polymer dispersion. In this case, the composition of the invention is preferably formulated as a two-pack formulation of a powdery composition (I) containing the components A, B, C and optionally E and F as the first part of the formulation, and a liquid composition (II) containing the aqueous polymer dispersion of the polymer P as the separately formulated second part of the formulation.

[0244] In the case of pulverulent polymer P, the composition of the invention can in principle also be formulated as a two-pack formulation. However, preference is given to formulating the composition of the invention as a physical mixture of the pulverulent composition components A, B, C and optionally E and F with the pulverulent polymer P.

[0245] The compositions of the invention in the form of physical mixtures are obtained by intimately mixing the various components in suitable mixing apparatus.

[0246] Furthermore, the present invention relates to the use of the composition of the present invention for providing a waterproof membrane and to a method for providing a waterproof membrane, the method comprising mixing components A, B, C, D and optionally E and F with water to obtain a flowable slurry and applying the flowable slurry to a surface requiring a waterproof membrane.

[0247] In the process of the present invention, the amount of water is preferably selected such that the weight ratio of water to pozzolanic material is in the range of 1:1 to 2:1.

[0248] The covering obtained after the applied material has solidified is waterproof and resistant to acidic substances, alkaline substances and chlorine-containing substances, such as various chloric acids, for example hypochlorous acid, as appearing in swimming pools and other water tanks, where the water has been treated for antifouling. The covering has a high bond strength and also has high flexibility and elasticity at low and very low temperatures. This makes the composition of the invention particularly suitable for all types of surfaces that come into contact with water, such as rainwater drains, sewage pipes, drains or tunnels, waterproof layer coverings under tiles in wet rooms, swimming pools and other water tanks. The composition is also suitable as a repair material for such coverings.

[0249] The present invention is further illustrated by the following examples.

[0250] Example

[0251] 1. Materials :

[0252] - Coarse tuff powder from Meurin, Germany; particle size < 100 μm

[0253] - CEM I 52.5R: Portland cement from HeidelbergCement AG, Germany.

[0254] - CEM I 52.5N: Portland cement from HeidelbergCement AG, Germany.

[0255] - Tuff cement: a mixture of volcanic tuff and Portland cement clinker in a weight ratio of 40:60 (Quick Mix TZ from Sievert Baustoffe GmbH, Germany)

[0256] -Brick powder: from Kalk, Germany; particle size < 250 μm; produced from waste bricks and tiles

[0257] -From CaO powder from Kalk, Germany 1; Precal 30N; particle size <90 μm

[0258] -From CaO powder from Kalk, Germany 2; Precal 641; particle size <90 μm

[0259] -Sand 1: particle size 0.06mm-0.2mm

[0260] -Sand 2: particle size 0.2mm-0.6mm

[0261] -Sand 3: F36; particle size 0.09mm-0.35mm

[0262] - Rubber powder type K0002 from MRH (Muelsener Rohstoff-und Handelsgesellschaft mbH), particle size < 0.23 mm; produced from waste tires

[0263] - HS1980; powdered thickener from BASF SE

[0264] - 5400; from BASF SE; aqueous anionic copolymer dispersion of a copolymer of acrylate and styrene; solid content: about 57%, Tg: -8°C; viscosity (250s at 23°C -1 ; DIN EN ISO 3219): 50mPa·s-350mPa·s, pH 5.5-7.5.

[0265] -Acronal From BASF SE; Aqueous self-crosslinking dispersion of a copolymer of acrylate and styrene; Solids content: about 53.5%, Tg: about -15°C; Viscosity (100 s at 23°C -1 ; DIN EN ISO 3219): 10mPa·s-100mPa·s, pH 5.5-8.5.

[0266] - SI2210: Defoamer from BASF SE

[0267] - AA 4135: Sodium polyacrylate dispersant from BASF SE

[0268] -Omyacarb 15GU: Limestone (calcium carbonate) powder from Omya

[0269] - DF 2922F: Powdered defoamer based on surfactants and minerals; from BASF SE

[0270] 2. Composition

[0271] 2.1 Compositions according to the invention

[0272] The following compositions of the invention are prepared by intimately mixing the ingredients in the amounts indicated below. Compositions (I) and (II) are formulated separately. Composition 1 consists of composition (I.1) and composition (II.1), composition 2 consists of composition (I.2) and composition (II.1), composition 3 consists of composition (I.3) and composition (II.1), composition 4 (not according to the invention) consists of composition (I.4) and composition (II.1), composition 5 consists of composition (I.5) and composition (II.1), composition 6 consists of composition (I.6) and composition (II.1), composition 7 consists of composition (I.7) and composition (II.1), and composition 8 consists of composition (I.8) and composition (II.2).

[0273] Table 1

[0274]

[0275]

[0276] *Not according to the present invention

[0277] 2.2 Comparative cementitious compositions

[0278] The following cementitious composition 9 (not according to the invention) was prepared by intimately mixing the ingredients in the amounts shown in Table 2.

[0279] Table 2

[0280]

[0281] 3. Application Testing

[0282] 3.1 Fresh characteristics

[0283] The fresh mix properties (density, pot life, workability and recoat time) were evaluated as follows:

[0284] a) Sample preparation

[0285] For this purpose, the corresponding compositions (I) and (II) given in Table 1 and Table 2 were mixed thoroughly. Mixing was carried out by means of a basket laboratory mixer at a speed of 600 1 / sec for 2 min, thereby obtaining a slurry that could be used for the production of waterproof coverings.

[0286] b) Determination of density

[0287] The density of the obtained slurry was measured at a temperature of 23°C using a 50 ml pycnometer. The pycnometer was first filled halfway with the slurry, then tapped three times on the laboratory bench to dislodge air bubbles and finally filled to the top. Any protruding material was scraped off with a mortar knife. The filled and empty pycnometers were weighed and the difference in mass was used to determine the density.

[0288] c) Evaluation of shelf life and processability

[0289] 300 g of the formulation were mixed in a 500 ml plastic cup (yogurt pot). The consistency of the material was checked with a spatula immediately after mixing. The creaminess and viscosity of the material were evaluated. The dripping from the spatula was also evaluated. In addition, the compound was applied to a concrete block with a 6 mm notched trowel and the processing characteristics were also evaluated.

[0290] At certain time intervals (immediately after 15 min, 30 min, 45 min, 60 min), partial amounts were removed from the 500 ml cup and tested for performance characteristics. If the substance could only be applied to the concrete block with considerable effort and poorly, the end of the storage period was reached. The results are summarized in Table 3.

[0291] d) Evaluation of recoating time at 23°C

[0292] To this end, the corresponding compositions A and B given in Table 1 were mixed thoroughly. The mixing was carried out by means of a basket laboratory mixer at a speed of 600 1 / sec for 2 min, thereby obtaining a slurry that can be used to produce a waterproof covering. Two welding wires with a diameter of 2.5 mm were placed at a distance of about 10 cm on a Teflon-coated plate and fixed with adhesive tape. The slurry thus obtained was applied to the gap with a scraper and then smoothed over the welding wires with a trowel. Thus, for wet application, the film thickness was 2.5 mm.

[0293] The test is carried out at 23°C and 50% humidity. The strength of the film is tested at intervals of about 30 min. For this purpose, the surface of the film is smoothed first by simple thumb pressure and then with a 6 mm toothed scraper under slight pressure. The "recoat time" is reached when no indentations or grooves appear on the surface of the film smoothed with the toothed scraper. The results are summarized in Table 3.

[0294] Table 3 :

[0295] Composition: 1 2 3 4* 5 6 7 8 9* Density [g / l] nd nd nd 1300 1393 1277 1321 1260 nd Storage period [min] 150 100 150 60 nd nd nd nd 140 Machinability qualified good qualified good good good good good good Recoating time [h] 6 4 6 3 4-5 4-5 4-5 4-5 6

[0296] *Not according to the invention; nd = not determined

[0297] 3.2 Mechanical properties of coating

[0298] The mechanical properties of the waterproofing membranes obtained from the compositions of the invention were measured in accordance with DIN EN 527-1 and DIN EN 527-2.

[0299] a) Sample preparation

[0300] To this end, the corresponding compositions A and B given in Table 1 were mixed thoroughly. The mixing was carried out by means of a basket laboratory mixer at a speed of 600 1 / sec for 2 min, thereby obtaining a slurry that can be used to produce a waterproof covering. Two welding wires with a diameter of 2.5 mm were placed at a distance of about 10 cm on a Teflon-coated plate and fixed with adhesive tape. The slurry thus obtained was applied to the gap with a scraper and then smoothed over the welding wires with a trowel. Thus, for wet application, the film thickness was 2.5 mm.

[0301] After 24 hours, the dried film was removed from the substrate. The film was dried for another 6 days at 23°C / 50% relative humidity. Three samples for dry storage (dumbbell S2) and three samples for wet storage (dumbbell S2) were then cut from the film of the dried sealing slurry using a punch.

[0302] b) Membrane properties after dry storage under ambient conditions

[0303] The samples obtained in a) were stored at ambient conditions (50% relative humidity and 23° C.) for 28 days. The mechanical properties were then determined by the protocol outlined in DIN EN 527-1 and DIN EN 527-2. For this purpose, the specimens were clamped in a testing machine and pulled at a speed of 50 mm / min. The elongation and the associated force were recorded. The results are summarized in Table 4.

[0304] c) Membrane performance after underwater storage (wet storage)

[0305] The samples obtained in a) were kept at ambient conditions for 7 days and subsequently stored in tap water at 23° C. for 21 days. The mechanical properties were then determined as outlined in b) above. The results are summarized in Table 4.

[0306] Table 4 :

[0307]

[0308] 1) Not according to the present invention

[0309] 3.3 Flexibility - Determination of the crack bridging properties of waterproof membranes obtained from the composition of the present invention at low temperatures

[0310] Crack bridging capacity at low temperatures tested according to DIN EN 14891.

[0311] For this purpose, the corresponding compositions (I) and (II) given in Table 1 and Table 2 were mixed thoroughly. Mixing was carried out by means of a basket laboratory mixer at a speed of 600 1 / sec for 2 min.

[0312] According to DIN EN 14891A8, the obtained mixture is directly applied to the mortar prism. After applying a very fine coating (spatula) and drying (about 20min), the first waterproof coating (wet thickness is 1.2mm) is applied. After drying (about 3h), the second layer (wet thickness is also 1.2mm) is applied. For each test formulation, three samples are prepared (3 samples are used for 23°C test, 3 samples are used for -5°C test and 3 samples are used for -20°C test). According to DIN EN 14891, it is then dried for 28 days at 23°C / 50% relative humidity. After the drying period, the sample cracks in a way that only the substrate cracks. The samples measured at -5°C and -20°C are stored in a climate chamber for 4h. The sample is then placed in a tensile device and pulled apart at a defined rate according to EN 14891 without shearing until cracks are visible on the coating surface. The gap width at this point is measured and recorded. The wider the gap width, the higher the flexibility. The measurements at -5°C and -20°C were done in a climate chamber. The results are given as the average of 3 tests and are compiled in Table 5.

[0313] Table 5

[0314] Composition Gap width at 23°C [mm] Gap width at -20°C [mm] 1 1.93 0.78 2 1.60 0.79 3 1.83 0.83 4* 1.88 0.87 5 1.78 0.78 6 2.12 0.72 7 2.11 0.75 8 2.81 0.74 9* 1.90 0.60

[0315] *Not according to the present invention

[0316] It can be seen that the waterproofing membrane obtained from the composition of the present invention has excellent flexibility and crack bridging properties at -20°C compared to the waterproofing covering obtained from the prior art cementitious composition.

[0317] 3.4 Bond strength

[0318] The bond strength was measured in accordance with DIN EN 14891: 2017. The samples were measured after storage at ambient conditions, after storage in water and after storage in chlorinated water.

[0319] a) Sample preparation

[0320] For this purpose, the corresponding compositions (I) and (II) given in Table 1 and Table 2 were mixed thoroughly as described above.

[0321] The mixture obtained is applied directly to the mortar column according to EN 12004-2:2016 by first applying a fine coat (spatula) and drying (about 20 min), then applying a first waterproofing coat (wet thickness 1.2 mm) and after drying (about 3 h) a second coat (wet thickness also 1.2 mm). The coating thus allowed is allowed to cure for 24 h under ambient conditions. An adhesive coating is applied. After 5 min, 9 tiles of type V1 according to EN 14411:2016 are placed on the adhesive coating at a distance of 50 mm and pressed with a load of 20 ± 0.05 N.

[0322] b) Storage under ambient conditions (bond strength dry)

[0323] The samples obtained in a) were kept at ambient conditions for 27 days. The tie rod plates were then bonded to the tiles with a high-strength adhesive. After 28 days of storage of the whole, the bond strength was measured by applying a force at a constant rate of 250 ± N / s.

[0324] c) Storage under water (bond strength wet)

[0325] The samples obtained in a) were kept at ambient conditions for 7 days and subsequently stored in water at ambient temperature for 21 days. After drying, the plates of the tie rods were bonded and the bond strength was measured as described in b).

[0326] d) Storage under chlorine water (bonding strength chlorine water)

[0327] The samples obtained in a) were kept at ambient conditions for 28 days and then stored in chlorine water for 7 days. The chlorine water was prepared from 200 mg / l NaCl, 200 mg / l Na2SO4 and NaOCl maintained at a concentration of 0.3 mg / l to 0.6 mg / l. The pH was maintained at 6.5 to 7.8. After storage, the samples were rinsed with water and dried. After drying, the plates of the tie rods were bonded and the bond strength was measured as described in b).

[0328] e) Storage under KOH aqueous solution (bonding strength KOH aqueous solution)

[0329] The samples obtained in a) were kept at ambient conditions for 28 days and then stored in a 3 wt % aqueous potassium hydroxide solution at 40° C. for 14 days. After storage, the samples were rinsed with water and dried. After drying, the plates of the tie rods were bonded and the bond strength was measured as described in b).

[0330] The results are compiled in Table 6.

[0331] Table 6

[0332]

[0333]

[0334] *Not according to the present invention

[0335] 3.5 Water tightness

[0336] According to DIN EN 14891A7, but at a higher pressure of 2.5 bar, water tightness is measured. For this purpose, unglazed concrete specimens are prepared by a procedure similar to that described in DIN EN 14891A7 and kept at ambient conditions for 28 days. As described in Section 3.1, 3 hardened specimens are coated on one surface. The other surfaces are then sealed with shaft sealing rings. The inner diameter is 100mm. The sealing ring height is about 2cm. The upper side of the sealing ring is pressed against a steel plate, which has a pressurized water inlet in the middle. Observe the moisture penetration of the uncoated back side of the stone. The specimens are weighed and stored at a water pressure of 2.5 bar for 7 days and then weighed again. If the weight increase of the 3 specimens is less than 25g on average and if no penetrating water is observed on the back side, the coating is considered to be waterproof. Compositions 1 to 6, 8 and 9 show good water tightness and low water absorption at ≥2.5 bar. The test results are summarized in Table 7.

[0337] Table 7

[0338] Composition: 1 2 3 4* 5 Pressure 2,5 bar for 7 days tight tight tight tight tight Water absorption[g] 2 7 4 3 4

[0339] *Not according to the present invention

[0340] Table 7 continued

[0341] Composition: 6 7 8 9* Pressure 2,5 bar for 7 days tight Not tight tight tight Water absorption[g] 8 22 3 8

[0342] *Not according to the present invention

[0343] 3.6 Capillary water absorption

[0344] a) Sample preparation

[0345] To this end, the corresponding compositions (I) and (II) given in Tables 1 and 2 were mixed thoroughly, thereby obtaining a slurry that can be used to produce a waterproof covering. Two welding wires with a diameter of 2.5 mm were placed at a distance of about 10 cm on a Teflon-coated plate and fixed with tape. 300 g of the slurry thus obtained were applied to the gap with a scraper and then smoothed over the welding wires with a trowel. Thus, for wet application, the film thickness was 2.5 mm.

[0346] After 24 hours, the dried film was removed from the substrate. The film was dried for a further 28 days at 23°C / 50% relative humidity. Rectangular test specimens (5 cm x 10 cm) were then cut from the film of the dried sealing slurry.

[0347] The weight of the film was determined on a laboratory balance. Each film was then placed in a shallow rectangular bowl filled with tap water so that the film was completely covered with water. At a specific time, the film was removed from the bowl, patted with an absorbent cloth and weighed again. The change in weight was determined and recorded. The results are given as % weight increase based on the starting weight. The test results are summarized in Table 8.

[0348] Table 8: Water absorption after x days [%]

[0349] Composition: 1 2 3 4* 5 6 7 8 1 day 8.6 6.3 4.7 4.1 5.3 5.1 5.3 4.5 2 days 9.3 6.7 5.2 5.2 6.6 6.6 6.8 6.2 3 days 10.0 7.4 5.6 5.9 7.3 7.5 7.6 6.9 4 days 11.7 9.0 6.8 6.9 7.9 8.2 8.1 7.6 7 days 15.1 12.4 9.3 8.0 8.9 9.3 9.3 8.5 9 days 16.6 13.9 10.5 9.0 9.3 10.0 9.9 9.2 11 days 17.7 15.1 11.2 10.1 9.6 10.4 10.3 9.5 15 days 19.2 17.0 12.4 10.8 10.4 11.2 11.0 10.2

[0350] *Not according to the present invention

[0351] 3.7 Sliding pressure

[0352] The gap pressure test is carried out similarly to the procedure described in DIN EN 15820. Although this standard is intended for bituminous applications, it is also used in Germany for mineral building waterproofing.

[0353] The test is carried out as follows: a film of the waterproof composition is applied to a Teflon foil with a layer thickness of 4 mm (dry film thickness). After drying for 28 days, the film is then placed on a slit pressure plate (in contrast to the standard, a rectangular plate of 20×20 cm is used. The slit width is 1 mm and the slit length is 25 mm). A water pressure of 2.5 bar is then applied to the sealing surface for 24 hours. From the test results summarized in Table 9, it can be seen that the sealing films prepared from all compositions 1 to 9 provide good watertightness.

[0354] Table 9

[0355] Composition: 1 2 3 <![CDATA[4 2) ]]> 5 6 7 8 <![CDATA[9 2) ]]> <![CDATA[Sliding pressure result 1) > tight tight tight tight tight tight tight tight tight

[0356] 1) 2.5 bar water pressure for 24 h, measured after the membrane was dried for 28 days

[0357] 2) Not according to the present invention

[0358] 3.8 Low temperature flexibility (mandrel test)

[0359] Flexibility is tested according to DIN EN 15813. This standard is also often used for bituminous products, but is also applicable to mineral waterproofing.

[0360] A waterproof slurry membrane with a dry film thickness of 3 mm was prepared. The membrane had a width of 50 mm and a length of 200 mm. After drying for 28 days, the membrane and the test mandrel (see standard) were stored at 0°C for at least 1 h, and then the membrane was slowly bent over the mandrel within 3 s. The membrane must not tear during this process. The test results are summarized in Table 10.

[0361] Table 10

[0362] Composition: 1 2 3 <![CDATA[4 2) ]]> 5 6 7 8 <![CDATA[9 2) ]]> <![CDATA[Low temperature flexibility 1) > 1 1 1 1 1 1 1 1 1

[0363] 1 Measured at 0°C; 1 = pass (no cracks), 0 = fail (cracks)

[0364] 2) Not according to the present invention

[0365] 3.9 Early rain resistance

[0366] Early rain resistance was measured according to DIN EN 15816. For this purpose, the waterproofing was applied to the concrete blocks with a wet layer thickness of 3 mm. After a drying time of 4 hours or 8 hours, a water spray test was carried out. The spraying time was 15 min. The test conditions are summarized in Table 11. No leaching was observed in any of the test coatings prepared with one of the compositions 1 to 3 and 5 to 9.

[0367] Table 11

[0368] Composition: 1 2 3 <![CDATA[4 2) ]]> 5 6 7 8 <![CDATA[9 2) ]]> <![CDATA[Early rain resistance, drying time [h] 1) > 4 4 4 nd 8 4 8 8 8

[0369] 1) Spray with 2 bar water for 15 min; no leaching (drying for 4 or 8 hours before testing)

[0370] 2) Not according to the invention.

Claims

1. A composition for producing a mineral waterproof membrane, comprising: a) a powdered pozzolanic material as component A, the powdered pozzolanic material comprising powdered trachyte in an amount of at least 15% by weight of the total amount of component A; b) powdered cement as component B, said powdered cement comprising portland cement clinker in an amount of at least 15% by weight, based on the total amount of said component B; c) at least one pulverulent filler as component C; d) an organic polymer P in the form of an aqueous polymer dispersion or in the form of a polymer powder as component D, wherein the polymer P has a glass transition temperature Tg of up to +10°C, in particular in the range from -30°C to +10°C, especially in the range from -20°C to +5°C, as determined by the differential scanning calorimetry (DSC) method in accordance with ISO 11357-2:2013, The weight ratio of the powdered tuff to the portland cement clinker is in the range of 5:95 to 95:

5.

2. The composition of claim 1, wherein the powdered trachyte tuff is powdered volcanic trachyte tuff.

3. A composition according to any one of the preceding claims, wherein the pozzolanic material further comprises brick dust.

4. The composition according to claim 3, wherein component A comprises i. 15% to 90% by weight, based on the total amount of component A, of powdered trachyte, in particular powdered volcanic trachyte; and ii. Based on the total amount of component A, 10 to 85 wt% of brick powder.

5. A composition according to any one of the preceding claims, wherein component B comprises at least 45 wt.% of portland cement clinker.

6. The composition according to any of the preceding claims, wherein the weight ratio of the powdered trachyte to the portland cement clinker of component B is in the range of 10:90 to 90:10, in particular in the range of 20:80 to 80:

20.

7. The composition according to any one of the preceding claims, wherein the weight ratio of component A to component B is in the range of 25:75 to 95:5, in particular in the range of 30:70 to 85:15, in particular in the range of 40:60 to 80:

20.

8. The composition according to any one of the preceding claims, wherein the total amount of component A and component B is in the range of 35 wt% to 65 wt%, based on the total weight of component A, component B and component C.

9. The composition according to any one of the preceding claims, wherein the component C comprises sand, in particular a combination of medium sand and fine sand.

10. The composition according to claim 8, wherein the component C further comprises an organic powdered recycled material, such as powdered rubber.

11. The use according to any one of the preceding claims, further comprising as component E powdered kaolin.

12. A composition according to any one of the preceding claims, further comprising as component F non-slaked lime.

13. The composition according to claim 12, wherein the amount of the non-slaked lime is in the range of 5 wt% to 20 wt% based on the total weight of the component A, component B and component C.

14. The composition according to any one of claims 1 to 11, which contains no non-slaked lime or less than 5% by weight of non-slaked lime based on the total weight of the components A, B and C.

15. The composition according to any of the preceding claims, wherein the polymer P is selected from the group consisting of styrene-butadiene copolymers, vinyl acetate homopolymers and copolymers, styrene-acrylate copolymers and all-acrylic copolymers.

16. A composition according to any one of the preceding claims, wherein the polymer of the polymer dispersion is made from ethylenically unsaturated monomers M comprising i. 80% to 99.9% by weight, based on the total amount of monomers M, of at least one monomer M1, the at least one monomer selected from the combination of at least one monovinyl aromatic monomer M1a and at least one further monomer M1b, the at least one further monomer selected from conjugated aliphatic dienes, alkyl acrylates or methacrylates and cycloalkyl acrylates or methacrylates and mixtures thereof, ii. 0 to 15% by weight, based on the total amount of monomers M, of one or more monomers M2, the one or more monomers are selected from monoethylenically unsaturated neutral monomers having a solubility in water of at least 60 g / L at 20° C., iii. 0% to 2% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M3, the one or more monoethylenically unsaturated monomers having at least one acid group; iv. 0% to 5% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M4, said one or more monoethylenically unsaturated monomers affecting the self-crosslinking of the polymer; v. 0% to 1.0% by weight, based on the total amount of monomers M, of one or more monoethylenically unsaturated monomers M5, the one or more monoethylenically unsaturated monomers having hydrolyzable silane groups; The total amount of the monomer M2, the monomer M3, the monomer M4 and the monomer M5 is in the range of 0.1 wt % to 20 wt % based on the total amount of the monomer M.

17. The composition according to any one of the preceding claims, wherein the relative amount of the polymer P of component D to the total weight of component A, component B, component C and, if present, the optional component E and component F is in the range of 1:10 to 1:1, in particular in the range of 1:6 to 1:1.

1.

18. Composition according to any of the preceding claims, wherein the relative amount of the organic polymer P in the composition for producing the waterproof membrane is present in an amount ranging from 10% to 50% by weight, in particular ranging from 15% to 45% by weight, based on the total weight of the dry matter of the composition for producing the waterproof membrane and calculated as polymer P.

19. A composition according to any preceding claim further comprising a polymeric dispersant.

20. A composition according to any one of the preceding claims, wherein the composition is formulated as a two-pack formulation, wherein a powdered composition (I) is a first part of the composition and a liquid composition (II) is a separately formulated second part of the composition, wherein the powdered composition (I) contains the components A, B and C and the optional components E and F if present, and wherein the liquid composition contains the polymer as an aqueous polymer dispersion.

21. A composition according to any one of claims 1 to 19, wherein the composition is formulated as a powdery formulation comprising the components A, B and C and the polymer P of component D and the optional components E and F if present.

22. Use of a composition according to any one of the preceding claims for producing a mineral waterproofing membrane.

23. A method for producing a mineral waterproofing membrane, the method comprising providing a composition according to any one of claims 1 to 21 in the form of an aqueous slurry of the components of the composition and applying the aqueous slurry to a surface requiring a waterproof covering.

Citation Information

Patent Citations

  • Continuous removal of monomer from aqueous suspension or dispersion

    DE19621027A1

  • Removal of malodorous organic cpds. from dispersion

    DE19624299A1

  • Reducing residual monomer content of e.g. acrylic polymers

    DE19741184A1

  • Reducing residual monomer content in aqueous polymer dispersion

    DE19741187A1

  • Aqueous polymer dispersion useful as binder agent for pigments for interior and exterior paints

    DE19805122A1